Plasma-treated single atom catalysts, their preparation and use

By adopting non-thermal plasma treatment technology on metal oxide support, uniform dispersion of precious metal atoms is achieved, the problem of unstable nanoparticle catalysts at high temperatures is solved, the stability and activity of the catalyst are improved, and the cost is reduced.

JP2025503549AActive Publication Date: 2025-02-04MAX PLANCK GESELLSCHAFT ZUR FOERDERUNG DER WISSENSCHAFTEN EV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024539621
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-30
Filing Date
2022-12-22
Publication Date
2025-02-04
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

In the prior art, nanoparticle catalysts are not stable enough in high temperature and reduction environments, and are prone to aggregate into larger particles, resulting in a decrease in catalytic efficiency and high cost of using precious metals.

Method used

The non-thermal plasma treatment method is used to uniformly disperse precious metal atoms on the metal oxide support to form a single atom catalyst. By performing non-thermal plasma treatment in the presence of oxygen, the noble metal atoms are ensured to be stable in the catalyst surface.

Benefits of technology

The stability and activity of the catalyst are improved, the amount of precious metals is used, the cost is reduced, while maintaining efficient catalytic performance at lower reaction temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503549000001_ABST
    Figure 2025503549000001_ABST
Patent Text Reader

Abstract

The present invention relates to a catalytically active material, its preparation and its use, for example in the catalytic oxidation of CO to CO2 or in the catalytic hydrogenation of alkynes, which comprises a support comprising a metal oxide and a noble metal atomically dispersed on the surface of said support, said metal oxide being selected from TiO2, CeO2, ZnO, SnO2, Ga2O3, In2O3, ZrO2 and Fe2O3, said noble metal being selected from Pt, Pd, Rh and Au, and the catalytically active material being obtained by a process comprising a step of non-thermal plasma treatment in the presence of O2.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalytically active material, to a process for its preparation and to uses of the catalytically active material. [Background technology]

[0002] Catalytic selective hydrogenation of alkynes to alkenes is an industrially important reaction. For example, hydrogenation of acetylene to ethylene is an important process in removing acetylene from the ethylene feed for polyethylene production, because the catalysts used in the production of polyethylene are poisoned by acetylene in the ethylene feed. In the hydrogenation of alkynes, catalysts based on nanoparticles containing noble metals such as Pt and Pd are used. For example, European Patent Application EP2060323A1 reports the use of intermetallic Pt / Ga nanoparticles.

[0003] Catalytic oxidation of CO to CO2 is important for pollution control in the automotive industry. Noble metals such as Pt, Pd, Rh and Au are known to be particularly active in catalytic CO oxidation reactions. Because noble metals are expensive, CO oxidation catalysts usually contain highly dispersed noble metal nanoparticles supported on metal oxides. European Patent Application No. EP0602865A1, for example, relates to CeO2 as a support material for catalysts. Compared to such nanoparticle catalysts, single atom catalysts (SACs) are generally considered advantageous because they maximize the noble metal efficiency. Because catalysis is a surface reaction process, the use of smaller metal particles can save costs and / or result in better catalyst selectivity / activity.

[0004] However, as described in US Patent Application No. US 2021 / 0016256A1, small metal particles, clusters or single atoms are not thermodynamically stable and usually sinter to form larger particles during catalytic reactions, especially at high temperatures and in reducing environments. Typical inert refractory support materials (e.g., SiO2, Al2O3, etc.) are used as high surface area supports, but usually do not firmly fix small metal clusters or single metal atoms. Against this background, US Patent Application Publication No. US2021 / 0016256A1 proposes a method for synthesizing nanocomposite catalysts using deposition of small clusters and nanoparticles of reducible oxides (CeOx, FeOx, NbOx, etc.) on inert refractory support materials selected from silica, alumina, magnesia, zirconia, cordierite, mullite, perovskite, or any combination thereof. One or more atoms of Pt, Au, Pd, etc. are deposited on such "nanocomposites" via strong electrostatic adsorption (SEA) from aqueous solutions. The synthesis of nanocomposite catalysts requires a calcination step, e.g., at 400 or 600 °C under air.

[0005] US Patent Application Publication No. 2021 / 0016256A1 describes a 0.05 wt% Pt / CeO x It has been claimed that single-atom catalysts of Pd1 / CeOx-SiO2 or 0.05 wt%Pd1 / CeOx-SiO2 have been synthesized. Increasing the Pt loading up to 2 wt% resulted in the formation of Pt clusters and nanoparticles.

[0006] Thus, there is a need for high metal loading SACs that not only exhibit excellent activity and selectivity, but are also stable under catalytically relevant conditions. Summary of the Invention [Problem to be solved by the invention]

[0007] It is an object of the present invention to provide a catalytically active material that can be effectively used for the oxidation of CO. Another object is to provide a catalytically active material suitable for the oxidation of CO, which exhibits high activity and / or stability in this reaction.

[0008] In another aspect, it is an object of the present invention to provide a catalytically active material that can be effectively used for the hydrogenation of alkynes. Yet another object is to provide a catalytically active material suitable for the hydrogenation of alkynes, which exhibits high activity, high selectivity and / or stability in this reaction.

[0009] In another aspect, it is an object of the present invention to provide a simple and effective method for preparing such catalytically active materials which can be suitably used. [Means for solving the problem]

[0010] The inventors of the present application have found that the above-mentioned problems can be solved by the following embodiments.

[0011] [1] A catalytically active material comprising: A support comprising a metal oxide; a noble metal atomically dispersed on the surface of said support; having the metal oxide is selected from TiO2, CeO2, ZnO, SnO2, Ga2O3, In2O3, ZrO2, and Fe2O3; the noble metal is selected from Pt, Pd, Rh, and Au; The catalytically active material is obtainable by a process comprising a step of non-thermal plasma treatment in the presence of O2. [2] The number of precious metal atoms normalized to the surface area of ​​the catalytically active material is 3.0×10 12 at / cm 2 From 8.0×10 14 at / cm 2 , preferably 3.0 x 10 12 at / cm 2 From 4.0×1014 at / cm 2 , more preferably 6.0×10 12 at / cm 2 From 2.0×10 14 at / cm 2 The catalytically active material according to [1], [3] the relative intensity of the noble metal in oxidation state X relative to the total intensity of the noble metal in all oxidation states in the catalytically active material, as measured by X-ray photoelectron spectroscopy, is 50% or more, preferably 75% or more; The catalytically active material according to [1] or [2], wherein X is 2+ for Pt and Pd, and 3+ for Rh and Au. [4] The infrared absorption spectrum measured for the catalytically active material has a peak at 2085 cm -1 From 2120cm -1 exhibits an absorption band in the range of (1) exposing said catalytically active material in a reaction cell to a reaction mixture containing 1% CO and 5% O2 at 1 bar, balanced with Ar; (2) heating the catalytically active material to 500 K at a rate of 60 K / min and reacting the mixture at 1 bar and 500 K for 5 min; (3) cooling the reaction mixture and the catalytically active material to 300K; (4) removing the reaction mixture from the reaction cell; and -9 Applying ultra-high vacuum (UHV) conditions of up to mbar; (5) recording spectra under ultra-high vacuum (UHV) at 300 K without additional exposure to CO; (6) increasing the temperature to 500K at a rate of 60K / min and recording spectra at 320K, 360K, 400K, 440K, 480K and 500K; and (7) Comparing the absorption maxima in the spectra recorded at each temperature. The catalytically active material according to any one of [1] to [3], which does not change when the catalytically active material is heated from 300 K to 500 K when measured by a thermal expansion coefficient (Tc) of 1.0 or more. [5] The metal oxide and the precious metal are selected from the following combinations of materials: The metal oxide is selected from TiO2 and CeO2; and The noble metal is selected from Pt and Pd. is selected from The catalytically active material according to any one of [1] to [4], wherein the metal oxide is preferably CeO2 and the precious metal is preferably Pt. [6] The catalytically active material according to any one of [1] to [5], wherein the support is in the form of particles, for example a powder. [7] The catalytically active material according to [6], wherein the support is composed of the metal oxide. [8] The catalytically active material according to [6] or [7], wherein the powder support has an average particle size of 10 nm to 50 nm as measured by scanning transmission electron microscopy, and is preferably a CeO2 powder support. [9] The catalytically active material according to any one of [6] to [8], comprising the support and the precious metal.

[10] The catalytically active material according to any one of [1] to [5], wherein the support is in the form of a membrane.

[11] The support includes a substrate and a cluster supported on the substrate; the substrate and the clusters comprise the same metal oxide; 10. The catalytically active material according to claim 10, wherein the average diameter of the clusters is equal to or less than 2.0 nm, preferably equal to or less than 1.5 nm, as determined by scanning tunneling microscopy.

[12] The catalytically active material according to

[11] , wherein the substrate and the clusters are composed of the same metal oxide.

[13] Use of the catalytically active material according to any one of [1] to

[12] in the catalytic oxidation of CO to CO2, The catalytically active material is preferably A gas mixture comprising CO and O2 is used to react in the presence of said catalytically active material at a pressure of 0.8 to 2.0 bar and a reaction temperature of 323 K to 573 K; The content of CO in the mixed gas is 5% by volume or less, The O2 content in the mixed gas is 2% by volume or more and 25% by volume or less, The CO / O2 molar ratio is preferably 2.0 or less when used.

[14] Use of the catalytically active material according to any one of claims [1] to

[12] in the catalytic hydrogenation of alkynes, The catalytically active material is preferably A gas mixture comprising an alkyne and H2 is used to react in the presence of said catalytically active material at a pressure of 0.8 to 2.0 bar and a temperature of 323 K to 573 K; The content of the alkyne in the mixed gas is 10% by volume or less, the molar ratio of alkyne to H2 in the mixed gas is 1 or less; The alkyne is preferably a C2 to C5 alkyne, more preferably a C2 to C3 alkyne.

[15] A method for producing the catalytically active material according to any one of [6] to [9], comprising the steps of: (1) providing a precursor of said catalytically active material having a support in the form of particles comprising a metal oxide and a precious metal on a surface of said support; (2) calcining the precursor for the catalytically active material in the presence of O; (3) performing a non-thermal plasma treatment of the calcined precursor for the catalytically active material in the presence of O2; The method comprising:

[16] The step (1) includes the following steps: (1a) depositing a precious metal onto the support, preferably from an aqueous solution of a salt of the precious metal, the support preferably consisting of an oxide of the metal; and (1b) co-precipitating the precious metal and the metal oxide from an aqueous solution containing salts of the precious metal and the metal oxide; The method according to

[15] , wherein the selected

[17] The method according to

[15] or

[16] , wherein the non-thermal plasma treatment is carried out at a pressure of 20 mbar or less and an O2 content of 5 vol.% or more.

[18] A method for producing a catalytically active material according to any one of claims

[10] to

[12] , selected from methods A and B. Method A is (1) providing a metal oxide membrane support; (2) performing a non-thermal plasma treatment in the presence of O2 to obtain a plasma-treated metal oxide membrane support; and (3) depositing a noble metal on the plasma-treated metal oxide membrane support in the gas phase, preferably by physical vapor deposition of said noble metal atoms; Including, Method B is (1) providing a metal oxide membrane support; (2) depositing a precious metal onto the metal oxide membrane support from a solution containing the precious metal; (3) performing a non-thermal plasma treatment in the presence of O; Including, The non-thermal plasma treatment is preferably performed at a concentration of 1×10 -6 mbar to 1×10 -5 The method is carried out at a pressure of 10 ... mbar.

[0012] When referring to preferred embodiments / features in this application, including all levels of preferred aspects, combinations of these preferred embodiments / features are also considered to be disclosed, insofar as such combinations of preferred embodiments / features make technical sense.

[0013] In this application, the use of the terms "having" or "including" should be understood to disclose, as a more limited embodiment, the term "consisting of", insofar as this has technical meaning.

[0014] When preferred upper and lower limits are given for certain features, this should be understood to disclose any combination of the upper and lower limits.

[0015] Hereinafter, depending on the context, the term "catalytically active material" may be interchangeable with "catalyst." [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a schematic diagram of the setup used to perform O2 plasma treatment on samples in film (A) and particle (B) morphology. [Diagram 2] (Left) Low-energy electron diffraction (LEED) patterns (measured at 81 eV) of the "CeO2-plasma" film support of Reference Example 4, the "CeO2-step" film support of Reference Example 3, the "CeO2-red" film support of Reference Example 2, and the "CeO2(111)" film support of Reference Example 1 (top to bottom). (Right) Pt 4f X-ray photoemission spectra (XPS) obtained for the Pt / CeO2-plasma sample of Example 1, the Pt / CeO2-step sample of Comparative Example 3, the Pt / CeO2-red sample of Comparative Example 2, and the Pt / CeO2(111) sample of Comparative Example 1 (top to bottom) before and after the CO oxidation reaction (10 mbar CO, 50 mbar O2, He balance to 1 bar, 523 K). The pre-reaction Pt 4f XPS was measured after annealing the sample at 523 K under ultra-high vacuum (UHV) at a pressure of 10-9 mbar. [Diagram 3]Pt 4f, Ce 3d, and O 1s XPS spectra of a Pt / CeO2(111) film sample from Comparative Example 1: (i) Measured at 300 K after the Pt deposition step; (ii) Measured during the UHV annealing step immediately after reaching a temperature of 523 K; (iii) After UHV annealing at 523 K for 5 min; (iv) After the CO oxidation reaction; (v) Ce 3d XPS spectrum normalized to the intensity of the peak at 882 eV. Regions of spectral change are highlighted by grey boxes. The relative amount of Ce3+ is indicated adjacent to the spectrum. [Figure 4] Pt 4f, Ce 3d, and O 1s XPS spectra of the Pt / CeO2-red film sample according to Comparative Example 2. (i) Measured at 300 K after the Pt deposition step. (ii) Measured during the UHV annealing step immediately after reaching a temperature of 523 K. (iii) After UHV annealing at 523 K for 5 min. (iv) After the CO oxidation reaction. (v) Ce 3d XPS spectrum normalized to the intensity of the peak at 882 eV. The areas of spectral change are highlighted by grey boxes. The relative amount of Ce3+ is indicated adjacent to the spectrum. [Diagram 5] Pt 4f, Ce 3d, and O 1s XPS spectra of a Pt / CeO2-step film sample according to Comparative Example 3: (i) measured at 300 K after the Pt deposition step; (ii) measured during the UHV annealing step immediately after reaching a temperature of 523 K; (iii) after 5 min UHV annealing at 523 K; (iv) after the CO oxidation reaction; (v) Ce 3d XPS spectrum normalized to the intensity of the peak at 882 eV. Areas of spectral change are highlighted by grey boxes. The relative amount of Ce3+ is indicated in the vicinity of the spectrum. [Figure 6]Pt 4f, Ce 3d, and O 1s XPS spectra of a Pt / CeO2-plasma film sample according to Example 1. (i) Measured at 300 K after the Pt deposition step. (ii) Measured during the UHV annealing step immediately after reaching a temperature of 523 K. (iii) After UHV annealing at 523 K for 5 min. (iv) After the CO oxidation reaction. (v) Ce 3d XPS spectrum normalized to the intensity of the peak at 882 eV. Regions of spectral change are highlighted by grey boxes. The relative amount of Ce3+ is indicated adjacent to the spectrum. [Figure 7] (a) STM images of the CeO2(111) film support from Reference Example 1 and (b, c) CeO2-plasma film supports from Reference Example 4, each measured at UHV, 523 K. (d) Topography profile along the line marked in STM image (c). (e) O 1s XPS spectrum of the CeO2-plasma film support from Reference Example 4 measured with standard (upper spectrum) and grazing (lower spectrum) radiation. (f) Binding energy shifts of peroxo-O atoms (open symbols) at the surface of CeO2 and of surface O atoms (filled symbols) of CeO2, relative to lattice O atoms in bulk CeO2 (set to zero), calculated for CeO2(111), CeO2(110) and CeO2(100) surfaces, respectively. The latter are abundant and occupy the majority of the experimental spectra. The shaded areas highlight the experimentally measured BE shifts. The insets show top views of the uppermost layers in density functional theory (DFT) optimized structures containing ¼ monolayers of peroxide species on the (111), (110), and (100) surfaces. [Figure 8] Top view, schematic of pristine (100), (110), (100), and (100)-4O surfaces of CeO2 (top) and schematic of peroxide species formed on the same surfaces of CeO2 by reaction with oxygen radicals (bottom). The oxygen-oxygen bond lengths are annotated. [Figure 9]Schematic of the (111), (110), (100), and (100)-4O surfaces of CeO2 with 0.5 monolayer peroxide coverage with diagonal and row-wise arrangement of peroxide species, viewed from the top. [Figure 10] 1 shows infrared reflection absorption spectra (IRAS) measured under ultra-high vacuum for (a) the Pt / CeO2(111) film sample (after annealing) according to Comparative Example 1, and (b) the Pt / CeO2-plasma film sample (after annealing) according to Example 1 with CO adsorption. [Figure 11] 1 shows (a) the Pt 4f XPS spectrum and (b) the O 1s XPS spectrum of the (annealed) Pt / CeO2-plasma film sample according to Example 1 and the (annealed) Pt / CeO2-sputtered film sample according to Comparative Example 4. [Figure 12] (a) CO oxidation rates measured for the "Pt / CeO2-plasma" film sample according to Example 1 and the "Pt / CeO2(111)" film sample according to Comparative Example 1, and their comparison with the "CeO2-plasma" and "CeO2(111)" film samples. (b) Pt 4f XPS spectra measured for the "Pt / CeO2-plasma" film sample according to Example 1 and the "Pt / CeO2(111)" film sample according to Comparative Example 1 after the CO oxidation reaction. [Figure 13] (a) Measured CO oxidation rates for plasma-treated Pt / CeO2 powder catalyst according to Example 2 and untreated Pt / CeO2 powder catalyst according to Comparative Example 5, and their comparison with "CeO2-plasma" and "CeO2" powder samples. Aberration-corrected scanning transmission electron microscope (STEM) images of plasma-treated Pt / CeO2 powder catalyst according to Example 2 before (b) and after (c) the CO oxidation reaction at 523 °C. Some Pt ​​single atoms are highlighted with circles. [Figure 14] 1 shows Pt 4f XPS spectra of (a) the plasma-treated Pt / CeO2 powder catalysts according to Examples 2 to 4, and (b) the untreated Pt / CeO2 powder catalysts according to Comparative Examples 5 to 7, measured after a CO oxidation reaction at 523 K for 3 hours. [Figure 15]1A and 1B are aberration-corrected STEM images of (a) untreated Pt / CeO2 powder catalyst according to Comparative Example 6, (b) plasma-treated Pt / CeO2 powder catalyst according to Example 3, (c) untreated Pt / CeO2 powder catalyst according to Comparative Example 7, and (d) plasma-treated Pt / CeO2 powder catalyst according to Example 4, measured after a CO oxidation reaction at 523 K for 3 hours. Pt single atoms are highlighted by dashed circles, and PtOx clusters are highlighted by solid circles. [Figure 16] (a) Raman spectra observed for an untreated CeO2 support from Reference Example 5 (labeled "CeO2 calcined") and a plasma-treated CeO2 support from Reference Example 6 (labeled "CeO2 plasma"). (b) Raman spectra observed for an untreated Pt / CeO2 catalyst from Comparative Example 5 (labeled "Pt / CeO2-calcined") and a plasma-treated Pt / CeO2 catalyst from Example 2 (labeled "Pt / CeO2-plasma"). All spectra are normalized to the maximum of the main peak at 465 cm-1 and vertically offset for clarity. [Figure 17] 1 shows ethene production rates observed for the plasma-treated Pt / CeO2 powder catalyst from Example 2 ("Pt / CeO2-plasma"), the untreated Pt / CeO2 powder catalyst from Comparative Example 5 ("Pt / CeO2-calcined"), as well as the Pt-free, calcined CeO2 powder support from Reference Example 5 ("CeO2-calcined"), and the plasma-treated CeO2 powder support from Reference Example 6 ("CeO2-plasma"). [Figure 18] 4f XPS spectra measured after UHV annealing at 523 K for 5 minutes for the Pt / CeO2-plasma film sample of Example 1, the Pt / CeO2(111) film sample of Comparative Example 1, the Pt / TiO2-plasma film sample of Example 5, and the Pt / TiO2(110) film sample of Comparative Example 8. [Figure 19] FIG. 13 is a schematic visualization of the restructuring of a CeO2(111) film resulting in the formation of CeO2 nanoclusters with a concomitant decrease in film thickness. [Figure 20]Robustness analysis of the final input parameters used in the thermodynamic model calculations. [Figure 21] Schematic of the energetically most favorable optimized structures of Pt atoms adsorbed on the (111), (110), (100), and (100)-4O surfaces of CeO2 with different peroxide coverages ranging from 0 (labeled "pris") to 1.0 monolayer (labeled "1.0"), all in top view. [Figure 22] Schematic of the stepped (112)b, (210), (211)a, (211)b, (221), (310), (311)a, and (311)b surfaces of CeO2 and adsorbed Pt atoms for the approximation of edge energies used in the thermodynamic model of ceria nanoparticle formation and consideration of alternative binding sites for monoatomic Pt. [Diagram 23] (a) Schematic of Pt atoms adsorbed at different sites of a CeO2 nanoparticle / membrane model composite system (Ce178O356, shown in the center). The adsorption energy (in eV; relative to bulk Pt) is shown adjacent to the structure. (b) Schematic of optimized geometries for CO adsorption on Pt single atoms at the CeO2 nanoparticle / interface and at (100)-4O (denoted as "Pt-4O"), (100)-3O (denoted as "Pt-3O"), and (100)-2O (denoted as "Pt-2O") sites. The Pt-3O and Pt-2O sites were created by removing one or more ligand oxygen atoms from Pt-4O. The CO adsorption energy (in eV) is shown. [Figure 24] Schematic of the boundary and (100)-4O of the CeO2 nanoparticle / slab model system, as well as Pt bound to the (100)-3O and (100)-2O sites derived from the (100)-4O site, and the calculated CO adsorption energy (in eV). [Diagram 25]Schematic of the interaction of Pt atoms with the CeO2(111) and CeO2-plasma membrane supports. Upon deposition on the CeO2(111) surface, Pt forms small clusters that agglomerate into larger Pt nanoparticles (NPs) at elevated temperatures (top row). Plasma treatment of the CeO2(111) surface in the presence of O2 generates peroxo species and induces surface reconstruction, resulting in small ceria NPs that act as anchor sites for Pt adsorption directly or through the surface transfer of peroxo-stabilized Pt single atoms (bottom row). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] (I. Catalytic active material) The catalytically active material of the present invention comprises a support comprising a metal oxide and a noble metal atomically dispersed on the surface of the support. The support comprises a metal oxide, the metal oxide being selected from TiO2, CeO2, ZnO, SnO2, Ga2O3, In2O3, ZrO2, and Fe2O3. The noble metal is selected from Pt, Pd, Rh, and Au. The catalytically active material is obtained by a method comprising a step of non-thermal plasma treatment in the presence of O2. The method comprises, for example, subjecting a support comprising a metal oxide and a noble metal on its surface to a non-thermal plasma treatment in the presence of O2. Alternatively, the support comprising a metal oxide is subjected to a non-thermal plasma treatment before the noble metal is deposited on its surface.

[0018] By "atomically dispersed" is meant the presence of single precious metal atoms on the surface of the support, which can be detected by conventional analytical techniques, such as extended X-ray absorption fine structure (EXAFS), infrared spectroscopy (IR), or STEM. STEM analysis is further explained in the experimental section. For the avoidance of doubt, unless otherwise stated, the term "atom" is used herein and in the claims to encompass both neutral (oxidation state=0) and charged (ionic, e.g., oxidized) precious metal atoms.

[0019] The form of the support is not particularly limited. The support may be, for example, in the form of particles (e.g., powder) or a film.

[0020] The invention is characterized in that the catalytically active material is obtained by a method comprising a step of non-thermal plasma treatment in the presence of O2.

[0021] In one embodiment, the catalytically active material of the present invention has a molecular weight of 815 to 845 cm -1 The Raman spectroscopy can be carried out according to the method described in the Examples. Without being bound by theory, it is believed that the Raman bands are centered in the range of 815-845 cm -1 The Raman bands centered in the range of 0.1 to 0.5 are due to surface peroxo(O2 2- ) species.

[0022] In one embodiment, the catalytically active material of the present invention exhibits an additional O 1s XPS signal at a binding energy of 1.2 eV to 2.0 eV, preferably 1.5 eV to 1.7 eV, higher than the main signal of oxygen of the metal oxide in the support. XPS analysis can be carried out according to the method described in the Examples. The additional XPS signal can be observed as a shoulder of the main signal. Without being bound by theory, it is believed that the additional XPS signal is due to surface peroxo(O2), which is preferably formed on the surface of the metal oxide during the non-thermal plasma treatment. 2- For example, in the case of the CeO2 support, the O 1s XPS signal of pristine (unplasma-treated) CeO2 appears at 529.2 eV, while the signal of the surface peroxo species appears at 530.8 eV.

[0023] In one embodiment, the non-thermal plasma treatment in the presence of O2 results in the formation of metal oxide nanoclusters on the support surface. The average diameter of the metal oxide nanoclusters may be 2.0 nm or less, preferably 1.5 nm or less, as determined by scanning tunneling microscopy (STM). See additional description below. STM measurements can be performed as described in the examples.

[0024] In one embodiment, the catalytically active material of the present invention exhibits two or more of the features described in the preceding embodiments.

[0025] In the present invention, the support comprises a metal oxide on the surface of the support, the metal oxide being selected from TiO2, CeO2, ZnO, SnO2, Ga2O3, In2O3, ZrO2 and Fe2O3. These metal oxides are often called reducible metal oxides. Reducible metal oxides can lose oxygen atoms from their crystal structure with relatively low energy, resulting in the formation of oxygen vacancies, and the oxidation number of the metal atom in the reducible metal oxide can be reduced to, for example, CeO2. 4+ From Ce 3+ The metal oxide is preferably selected from TiO2, CeO2, SnO2, Ga2O3, In2O3 and Fe2O3, more preferably selected from TiO2, CeO2 and In2O3, and most preferably CeO2.

[0026] Due to the support containing a reducible metal oxide, the catalytically active material of the present invention can exhibit excellent catalytic activity and stability, and can carry out the CO oxidation reaction at a relatively low reaction temperature. Without being bound by theory, it is believed that metal oxide nanoclusters are formed on the support surface during plasma treatment in the presence of O2, and the atomically dispersed noble metals strongly interact with the metal oxide. This interaction allows charge transfer, and the presence of oxygen atoms bridging the noble metal and the metal oxide is believed to provide excellent stability and excellent catalytic activity even at low reaction temperatures.

[0027] Another advantage of using certain reducible metal oxides (e.g., instead of SiO2) in the support is that the reducible oxides, such as CeO2, themselves may also contribute to catalytic activity in the catalyzed reaction, especially if the reducible metal oxide is plasma treated. In a preferred embodiment, CeO2 clusters are generated during plasma treatment of the CeO2 support, and thus metal atoms (e.g., Pt atoms) also interact with the active CeO2 support (e.g., when compared to SiO2). Furthermore, data presented in the Examples section show that CeO2 supports can be activated by plasma treatment even in the absence of noble metals, such as Pt. This finding can be attributed to the formation of small CeO2 clusters with high surface density, and possibly also the formation of peroxide surface species, for example, on the formed CeO2 clusters. These findings are transferable to other reducible metal oxides and noble metals used in the present invention.

[0028] The catalytically active material according to the invention comprises a noble metal atomically dispersed on the surface of the support, the noble metal being selected from Pt, Pd, Rh and Au. Preferably, the noble metal is selected from Pt and Pd. More preferably, the noble metal is Pt.

[0029] The combination of the metal oxide and the precious metal is not particularly limited. In a preferred embodiment, the metal oxide is selected from TiO2 and CeO2, and the precious metal is selected from Pt and Pd, and the combination of CeO2 and Pt is more preferred.

[0030] The number of noble metal atoms normalized to the surface area of ​​the catalytically active material (area density, Ns) is, but is not limited to, at least 3.0 × 10 12 at / cm 2 It is preferable that the ratio is at least 6.0×10 12 at / cm 2 More preferably, it is at least 1.2×10 13 at / cm 2 More preferably, the upper limit of Ns is 8.0×10 14 at / cm 2For example, 4.0×10 14 at / cm 2 may be 2.0 x 10 14 at / cm 2 , 1.0×10 14 at / cm 2 , 8.0×10 13 at / cm 2 , 6.0×10 13 at / cm 2 , or 4.0 × 10 13 at / cm 2 Any combination of the above upper and lower limits is an embodiment of the present invention. S For example, 3.0 x 10 12 at / cm 2 From 8.0×10 14 at / cm 2 , 3.0×10 12 at / cm 2 From 4.0×10 14 at / cm 2 , 3.0×10 12 at / cm 2 From 2.0×10 14 at / cm 2 , 6.0×10 12 at / cm 2 From 8.0×10 14 at / cm 2 , 60×10 12 at / cm 2 From 4.0×10 14 at / cm 2 Ns is 3.0×10 12 at / cm 2 From 8.0×10 14 at / cm 2 The range of 3.0×10 12 at / cm 2 From 4.0×10 14 at / cm 2 The range of 6.0×10 is more preferable. 12 at / cm 2 From 2.0×10 14 at / cm 2 More preferably, the range is N S A method for determining is given in the Examples section.

[0031] At least a portion of the noble metal preferably has a specific oxidation state X. The specific oxidation state X of the noble metal may result from a strong interaction with the metal oxide in the support. When the noble metal is Pt or Pd, the specific oxidation state X is 2+. When the noble metal is Rh or Au, the specific oxidation state X is 3+. The relative intensity of the noble metal having a specific oxidation state to the sum of the intensities of the noble metal in all oxidation states, as measured by X-ray photoelectron spectroscopy (XPS), is preferably 50% or more, more preferably 75% or more, even more preferably 80% or more, and particularly preferably 90% or more. For example, when the noble metal is Pt, Pt 0 , Pt 2+ and Pt 4+ of Pt relative to the total intensity (i.e., all observed oxidation states) 2+ The relative intensities of are determined from the Pt 4f XPS spectrum. The detailed determination method is described in the Examples section.

[0032] The infrared reflection absorption spectrum (IRAS) measured for the catalytically active material is -1 From 2120cm -1 This shows an absorption band in the range of 0.01 to 0.25 mm, which does not change upon heating the material from 300 to 500 K. It is measured under the following conditions: (1) exposing the catalytically active material in a reaction cell to a reaction mixture consisting of 1% CO and 5% O (balance with Ar) at 1 bar; (2) heating the catalytically active material to 500 K at a rate of 60 K / min and reacting the mixture at 500 K and 1 bar for 5 minutes; (3) cooling the reaction mixture and the catalytically active material to 300K; (4) Remove the reaction mixture from the reaction cell and add 10 -9 applying ultra-high vacuum (UHV) conditions of 0.1 mbar or less; (5) recording a spectrum at 300K, UHV, without further exposure to CO; (6) increasing the temperature at a rate of 60 K / min to 500 K and recording spectra at 320 K, 360 K, 400 K, 440 K, 480 K and 500 K; and (7) Comparing the absorption maxima in the spectra recorded at each temperature.

[0033] For any catalytically active material of the present invention, -1 From 2120cm -1 In the case of Pt / CeO2, the corresponding band (i.e., its absorption maximum) is in the range of 2110 cm to 2110 cm, as can be seen in FIG. -1 ±1cm -1 is located.

[0034] In the first embodiment of the present invention, the support is in the form of particles, for example forming a powder. The shape of these particles is not particularly limited and may be selected from ellipsoids, cubes and spheres.

[0035] In the first embodiment of the present invention, the average particle size of the support is preferably, but not limited to, 10 nm to 1 μm, more preferably 10 nm to 500 nm, even more preferably 10 nm to 100 nm, particularly preferably 10 nm to 50 nm, and most preferably 10 nm to 30 nm. The average particle size of the support can be determined by measuring the diameter of 20 randomly selected particles by STEM and calculating the average, as described in the experimental section. As the "diameter", the longest visible axis of the particle is taken. For further measurement accuracy, the measurement can be performed on 100 randomly selected particles. If several particles are together forming an aggregate, the diameter of the primary particle is taken for the measurement.

[0036] In a first embodiment of the invention, the support is preferably composed of a metal oxide selected from TiO2, CeO2, ZnO, SnO2, Ga2O3, In2O3, ZrO2, and Fe2O3. In a preferred aspect of the first embodiment of the invention, the catalytically active material is preferably composed of a metal oxide support and at least a portion of the precious metal atomically dispersed therein. In another preferred aspect of the first embodiment of the invention, the catalytically active material is preferably composed of a metal oxide support and at least 50%, at least 75%, at least 80%, or at least 90% of the precious metal atomically dispersed therein.

[0037] XPS can be used to measure the fraction of atomically dispersed precious metals. In particular, the relative intensity of a precious metal having a particular oxidation state X, as described above, to the total intensity of the precious metal in all oxidation states, can be taken as a feature that indicates the fraction of atomically dispersed precious metal. For example, if the precious metal is Pt, the fraction of atomically dispersed Pt is the ratio of Pt to the total intensity of Pt in all oxidation states. 2+ It can be determined from the relative intensity of Pt 0 and Pt 4+ can be attributed to metallic Pt and PtO2 clusters, respectively.

[0038] STEM can also be used to measure the percentage of atomically dispersed precious metals. In particular, 100 STEM photographs (e.g., magnifications up to 10 nm×10 nm) that clearly show precious metal species (atomically dispersed precious metals and clusters containing two or more precious metals) are arbitrarily selected, and the percentage of atomically dispersed precious metals is determined for each STEM photograph and then averaged. In the STEM photograph, the precious metal species may appear brighter than the support.

[0039] The proportion of atomically dispersed noble metal is preferably determined by XPS.

[0040] In the first embodiment of the present invention, the areal density Ns of the precious metal is preferably 3.0×10 12 at / cm 2 From 4.0×10 14 at / cm 2, more preferably 3.0×10 12 at / cm 2 From 2.0×10 14 at / cm 2 , and more preferably 3.0×10 12 at / cm 2 to 1.0×10 14 at / cm 2 , and even more preferably 6.0×10 12 at / cm 2 to 1.0×10 14 at / cm 2 It is.

[0041] In a second embodiment of the present invention, the support is in the form of a membrane. The membrane support may be provided on a substrate. In one embodiment, the substrate provides a planar area on which the membrane support can be grown, for example, by metal vapor deposition of a reducible oxide on the oxidized surface of the substrate. The substrate is not particularly limited, so long as it does not adversely affect the catalytically active material. For example, a substrate made of a metal, an alloy, or a ceramic may be used. Examples of metals used as substrates include, but are not limited to, Ru, Cu, Al, etc. The metals used as substrates may be single crystals, examples of which include Ru(0001) single crystal, Cu(111) single crystal, etc. Examples of alloys used as substrates include, but are not limited to, steel, brass, etc. Examples of ceramics used as substrates include, but are not limited to, alumina, silica, silicon carbide, etc. Those skilled in the art can select a substrate suitable for the reaction conditions to which the catalytically active material will be exposed. In the second aspect of the present invention, the thickness of the film support is not particularly limited, but is preferably 5 nm to 50 nm, and more preferably 10 nm to 20 nm. The thickness of the metal oxide film can be determined, for example, by measuring the attenuation of the XPS signal of the substrate on which the metal oxide film is provided, by XPS. For example, when the metal oxide film is provided on a Ru substrate, the attenuation of the Ru 3d signal in the XPS spectrum can be measured to determine the thickness of the metal oxide film support. Similarly, when a Cu substrate is used, the attenuation of the Cu 2p signal in the XPS spectrum can be measured. Similarly, when a steel substrate is used, the attenuation of the Fe 2p signal in the XPS spectrum can be measured. Those skilled in the art can suitably select signals arising from elements in the substrate and measure their attenuation to determine the thickness of the metal oxide film. Details of the measurement method are described in the Examples section.

[0042] In the second embodiment of the present invention, the areal density Ns of the precious metal is 3.0×10 12 at / cm 2 From 4.0×10 14 at / cm 2 It is preferable that the ratio is 6.0×10 12 at / cm2 From 4.0×10 14 at / cm 2 More preferably, it is 1.2×10 13 at / cm 2 From 2.0×10 14 at / cm 2 It is even more preferable that:

[0043] In a second embodiment of the invention, the support may be composed of a substrate and clusters supported on said substrate, the substrate and clusters comprising the same metal oxide. Preferably, the substrate and clusters are composed of the same metal oxide. The average diameter of the measured clusters may be 2.0 nm or less, preferably 1.5 nm or less. This is determined by STM by plotting the topographical profile along a line corresponding to a length of 10 nm, measuring the distance between two adjacent minima, multiplying the measurement by a correction factor of 0.5, recording the obtained value as the diameter, repeating the measurement for 20 arbitrarily selected surface areas showing coverage by metal oxide clusters, and calculating the average value. A detailed method is described in the Examples section.

[0044] The number of metal oxide clusters on a metal oxide substrate normalized by the surface area of ​​the metal oxide substrate (surface cluster density) is not particularly limited. The surface cluster density is at least 0.05 clusters / nm 2 More preferably, it is at least 0.08 particles / nm 2 More preferably, it is at least 0.10 particles / nm 2 More preferably, it is at least 0.12 particles / nm 2 Most preferably, the surface cluster density is equal to or greater than 100 nm. The surface cluster density can be determined by counting the number of metal oxide clusters present in an arbitrarily selected area using STM. Detailed methods are described in the Examples section.

[0045] In a preferred aspect of the second embodiment of the present invention, the catalytically active material preferably comprises, for example, at least 50%, at least 75%, at least 80% or at least 90% atomically dispersed precious metal, the proportion of atomically dispersed precious metal being determined as described above for the first embodiment.

[0046] The catalytically active material of the present invention is particularly suitable for the oxidation of CO and the selective hydrogenation of alkynes (e.g., acetylene hydrogenation). The catalytically active material of the present invention is also suitable for other catalytic reactions, including, for example, the water gas shift reaction, steam reforming, and the oxidation of natural gas.

[0047] The catalytically active materials of the present invention exhibit excellent stability and activity, which is also reflected by the favorably low onset reaction temperatures in target reactions such as CO oxidation and selective alkyne hydrogenation. At least in part, these properties appear to be related to the atomic dispersion of the noble metals on the surface of the metal oxide clusters. Available experimental evidence further supports this atomic dispersion and / or noble metal loading (at / cm 2 It is shown that the uniformity of the crystalline structure (C) can be improved by the method of the present invention for producing a catalytically active material as follows.

[0048] II. Methods for Producing Catalytically Active Materials The method for producing a catalytically active material according to a first embodiment of the present invention may comprise the following steps: (1) providing a precursor of a catalytically active material comprising a support in the form of particles comprising a metal oxide and a precious metal on the surface of said support; (2) calcining a precursor of a catalytically active material in the presence of O2; and (3) performing a non-thermal plasma treatment of the calcined precursor of the catalytically active material in the presence of O2.

[0049] At the end of step (1), the noble metal may be present on the surface of the support in elemental form (oxidation state=0) or as a noble metal compound, e.g., a noble metal salt. The method for providing the precursor of the catalytically active material is not particularly limited, but it is preferred that step (1) is selected from the following steps (1a) and (1b): (1a) depositing a noble metal on a support; and (1b) co-precipitating a precious metal and a metal oxide from an aqueous solution containing salts of the precious metal and the metal oxide.

[0050] The method of depositing the precious metal on the support in step (1a) is not particularly limited and includes, for example, physical vapor deposition, chemical vapor deposition, precipitation from an aqueous solution of a salt of the precious metal, etc. The precious metal is preferably deposited on the support from an aqueous solution of the salt of the precious metal, and known methods such as strong electrostatic adsorption (SEA) and impregnation may be used as appropriate. The deposition is preferably carried out so that the deposition of the precious metal can be controlled with respect to the surface density of the metal atoms on the support. In step (1a), the support is preferably composed of a metal oxide.

[0051] The salt of the noble metal is not particularly limited. Examples of the salt of the noble metal include, but are not limited to, tetraammineplatinum(II) nitrate, tetraammineplatinum(II) chloride, platinum acetylacetonate(II), tetraammineplatinum(II) nitrate, tetraamminepalladium(II) chloride, acetylacetonate rhodium(III), tetrachloroauric(III) acid, and gold(III) chloride.

[0052] As used herein, the terms "calcining" or "calcination" refer to the heat treatment of a solid at an elevated temperature in the presence of O2 under dry conditions. As used herein, the term "dry" indicates that no additional water is introduced into the atmosphere in which the calcination is carried out. For example, calcination in air is understood to be carried out under dry conditions.

[0053] Calcination of the precursor of the catalytically active material is preferably carried out at a temperature of 573 K to 973 K, more preferably 623 K to 873 K, and even more preferably 673 K to 823 K. Calcination is preferably carried out at an O2 concentration of 5 vol.% or more, more preferably 10 vol.% or more. For example, air can be used as the O2 source.

[0054] The non-thermal plasma treatment of the calcined precursor of the catalytically active material is carried out in the presence of O2. Before ignition of the plasma, the pressure is preferably reduced to 40 mbar or less, more preferably to 20 mbar or less. The pressure during the non-thermal plasma treatment is preferably 40 mbar or less, more preferably 20 mbar or less. The non-thermal plasma treatment is preferably carried out with an O2 concentration in the inert gas of 5% by volume or more, more preferably 80% or more, even more preferably 100% (pure oxygen). The inert gas may be selected from N2, He, Ne, Ar, etc.

[0055] The non-thermal plasma treatment may be carried out in a static atmosphere or under gas flow, the latter being preferred. If the non-thermal plasma treatment is carried out under gas flow, the calcined catalytically active material precursor is preferably blown up (floated) by the gas flow during the non-thermal plasma treatment.

[0056] The source of the non-thermal plasma is not limited, and examples include inductively coupled plasma, capacitively coupled plasma, DC glow discharge, microwave plasma, radio frequency plasma, cold plasma jet, and dielectric barrier discharge plasma. The source of the non-thermal plasma is preferably a microwave plasma or a radio frequency plasma.

[0057] When the source of non-thermal plasma is a microwave plasma, the anode voltage of the plasma source is preferably 0.2 kV to 2 kV, and the emission current is preferably 0.1 μA to 1 μA.

[0058] When the source of non-thermal plasma is a high frequency plasma, the power of the high frequency plasma generator is preferably from 20W to 300W.

[0059] The time for the non-thermal plasma treatment can be appropriately adjusted as desired, but is usually 1 to 300 minutes, preferably 5 to 180 minutes, more preferably 10 to 120 minutes, and further preferably 30 to 90 minutes.

[0060] The method for producing the catalytically active material according to the second aspect of the present invention may be selected from the following methods A and B.

[0061] Method A has the following steps: (1) providing a metal oxide membrane support; (2) performing a non-thermal plasma treatment in the presence of O2 to obtain a plasma-treated metal oxide membrane support; (3) depositing a noble metal on the plasma-treated metal oxide film support in the gas phase, preferably by physical vapor deposition of noble metal atoms.

[0062] Method B comprises the following steps: (1) providing a metal oxide membrane support; (2) depositing a film of a precious metal on a metal oxide film support from a solution containing the precious metal; (3) performing a non-thermal plasma treatment in the presence of O2.

[0063] The method for providing the metal oxide film support is not particularly limited, and any method that has been conventionally used may be used. Methods for providing the metal oxide film include molecular beam epitaxy, laser ablation, chemical vapor deposition, sol-gel, etc. In one embodiment, the metal oxide film is provided on a substrate as described above with respect to the second embodiment of the present invention.

[0064] In step (2) of method A and step (3) of method B, the non-thermal plasma treatment is carried out in the presence of O2. The non-thermal plasma treatment is preferably carried out in the presence of O2 at a concentration of 1×10 -6 mbar to 1×10 -2 mbar, more preferably 1×10-6 mbar to 1×10 -4 mbar, more preferably 1×10 -6 mbar to 1×10 -5 The partial pressure of O2 during the non-thermal plasma treatment is preferably 1×10 -6 mbar to 1×10 -2 mbar, more preferably 1×10 -6 mbar to 1×10 -4 mbar, more preferably 1×10 -6 mbar to 1×10 -5 In one embodiment, the non-thermal plasma treatment is preferably carried out in 100% O2 at the above pressures.

[0065] The non-thermal plasma treatment may be carried out in a static atmosphere or under gas flow.

[0066] The source of the non-thermal plasma is not particularly limited, and may include, for example, inductively coupled plasma, capacitively coupled plasma, DC glow discharge, microwave plasma, high frequency plasma, cold plasma jet, and dielectric barrier discharge plasma. The source of the non-thermal plasma is preferably microwave plasma or high frequency plasma.

[0067] When the source of the non-thermal plasma is a microwave plasma, the anode voltage of the plasma source is preferably 0.2 kV to 2.0 kV, more preferably 0.5 kV to 1.5 kV, and the emission current is preferably 0.1 μA to 1.0 μA.

[0068] When the source of the non-thermal plasma is a high frequency plasma, the power of the high frequency plasma generator is preferably 20W to 300W.

[0069] The time for the non-thermal plasma treatment can be appropriately adjusted as desired, but is usually 1 to 300 minutes, preferably 5 to 180 minutes, more preferably 10 to 120 minutes, and further preferably 30 to 90 minutes.

[0070] In step (3) of method A, the method of depositing a precious metal on the plasma-treated metal oxide film support in the gas phase is not particularly limited, but examples include physical vapor deposition and chemical vapor deposition, and physical vapor deposition is preferred. In step (2) of method B, the method of depositing a precious metal on the plasma-treated metal oxide film from a solution containing the precious metal is not particularly limited, but one example includes precipitation from an aqueous solution of a precious metal salt as a precursor. When precipitating a precious metal from an aqueous solution, the method and material described in the method for producing a catalytically active material according to the first embodiment of the present invention can be applied.

[0071] In the method described herein, it can be assumed that all of the deposited precious metal is present on the surface of the metal oxide support and the metal oxide clusters, so that a high catalytic activity of the catalytically active material can be obtained with a low amount of precious metal.

[0072] (III. Catalytic Oxidation of CO) The catalytically active material of the present invention may be suitably used in the catalytic oxidation of CO to CO2 (also referred to as "catalytic oxidation").

[0073] In the catalytic oxidation of CO to CO2, a reaction gas mixture containing CO and O2 is reacted in the presence of a catalytically active material to produce CO2. The pressure of the reaction gas mixture is not particularly limited and may be from 0.8 bar to 2.0 bar, preferably from 0.8 to 1.5 bar, more preferably from 0.9 to 1.2 bar.

[0074] The reaction temperature of the catalytic oxidation is not particularly limited, and is from 323K to 573K, preferably from 353K to 523K, and more preferably from 353K to 473K.

[0075] The composition of the reaction gas mixture is not particularly limited as long as it contains CO and O2. The content of CO in the reaction gas mixture is, for example, 5 vol% or less, preferably 3 vol% or less, more preferably 2 vol% or less. The content of O2 in the reaction gas mixture may be 2 vol% or more and 25 vol% or less, preferably 5 vol% or more and 20 vol% or less. The molar ratio of CO / O2 in the reaction gas mixture is preferably 2.0 or less, more preferably 1.0 or less, even more preferably 0.5 or less, and most preferably 0.2 or less.

[0076] (IV. Catalytic Hydrogenation of Alkynes) The catalytically active material of the present invention can be suitably used for catalytic hydrogenation of alkynes to alkenes (also called "catalytic hydrogenation"). The alkynes used in catalytic hydrogenation are preferably C2-C5 alkynes, more preferably C2-C3 alkynes.

[0077] In the catalytic hydrogenation of alkynes to alkenes, a reaction gas mixture containing an alkyne and H2 is reacted in the gas phase in the presence of a catalytically active material to produce an alkene. For example, when acetylene (ethyne) is used as the alkyne, ethylene (ethene) is produced as the product (alkene).

[0078] The pressure of the reaction gas mixture is not particularly limited and may be from 0.8 bar to 2.0 bar, preferably from 0.8 to 1.5 bar, more preferably from 0.9 to 1.2 bar.

[0079] The reaction temperature of the catalytic hydrogenation is not particularly limited, but may be from 323K to 573K, preferably from 323K to 523K, and more preferably from 353K to 473K.

[0080] The composition of the reaction gas mixture is not particularly limited as long as it contains an alkyne and H2. The content of the alkyne in the reaction gas mixture may be, for example, 10% by volume or less, preferably 5% by volume or less, and more preferably 3% by volume or less. The content of H2 in the reaction gas mixture may be, for example, 3% by volume or more, 5% by volume or more, or 10% by volume or more. The molar ratio of H2 / alkyne is preferably 1.0 or more, and more preferably 2.0 or more.

[0081] (Example) The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0082] (Analysis method) Scanning tunneling microscopy (STM) analysis - average diameter and number of metal oxide clusters; and low-energy electron diffraction analysis (LEED) - surface ordering on the membrane support. STM measurements were carried out at a sample voltage of 3.8 V and a constant tunneling current of 30 pA.

[0083] To determine the average diameter of metal oxide clusters, such as CeO2 clusters, the topographical profile was plotted along a line corresponding to a length of 10 nm. In the topographical profile, the distance between two adjacent minima was measured and the measurement was multiplied by a correction factor of 0.5 to correct for the tip / cluster folding effect. The corrected value obtained was recorded as the diameter. The diameters of 20 randomly selected metal oxide clusters were measured and the average value was calculated.

[0084] To determine the surface density of metal oxide clusters, i.e. the number of metal oxide clusters normalized to the surface area of ​​the metal oxide substrate, in the recorded STM images, the number of metal oxide clusters in an arbitrarily selected area of ​​100 nm × 100 nm was counted. This measurement was repeated on four different sample spots, i.e., measurements were performed on a total of five different sample spots. The obtained average value was taken as the "density of metal oxide clusters".

[0085] Electron diffraction (LEED) analysis was performed on the same instrument and LEED patterns were recorded at 81 eV.

[0086] (Scanning Transmission Electron Microscopy (STEM) Analysis - Average diameter of metal oxide particles in powder) STEM images were taken using a 200 kV JEOL JEM ARM200F probe / image correction TEM (JEOL The data were recorded by the company.

[0087] The average diameter of the metal oxide particles, e.g., CeO2 particles, of the metal oxide powder support was determined by measuring the diameter of 20 randomly selected particles and calculating the average. If the selected particle showed a non-spherical shape in the STEM image, the longest axis was taken as the diameter.

[0088] (X-ray photoelectron spectroscopy (XPS) - elemental composition in catalytically active materials (films) and chemical (oxidation) state of elements at the surface) XPS measured the relative intensity of a precious metal having a specific oxidation state (X) to the total intensity of the precious metal in all oxidation states. For Pt, the specific oxidation state is 2+. In addition, when the catalytically active material is a film, XPS measured the number of precious metals per surface area of ​​the catalytically active material, N S (at / cm 2) were measured. XPS spectra were measured using an Al Kα X-ray source (hν=1486.6 eV) on a Phoibos 150 analyzer (SPECS GmbH). Spectral analysis (background subtraction and deconvolution) was performed using CasaXPS software (available from Casa Software Inc.; version 2.3.18), and the measured spectra were subjected to background subtraction using Shirley background. For the Pt / CeO2 film sample, Pt 4f, Ce 3d and O 1s core level spectra were recorded with pass energies of 25 eV, 50 eV and 50 eV, respectively. A person skilled in the art can use common general knowledge to select the core levels of the elements of interest and assign the binding energies to the oxidation states. Tabular lists of binding energies, such as those in the NIST X-ray photoelectron spectroscopy database, belong to the common general knowledge of a person skilled in the art.

[0089] The Pt spectra were subjected to spectral deconvolution analysis using CasaXPS software. Background subtraction was performed for each Pt spectrum in the range of 68 eV to 80 eV. The spectra were deconvoluted using a Gaussian / Lorentzian lineshape. The maximum full width at half maximum (FWHM) of each peak was set to 2.0 eV. 2+ The relative intensity of Pt 4f 7 / 2 The area was calculated as the percentage of the peak at 72.6 eV relative to the total peak area of ​​the signal.

[0090] (Metal oxide film thickness measurement) The thickness of a metal oxide film prepared on a substrate, e.g., a CeO2 film deposited on a Ru(0001) single crystal, was determined by XPS from the attenuation of the most intense signal originating from the substrate, e.g., the Ru 3d signal, compared to the signal of the substrate before the deposition of the CeO2 film.

[0091] (Raman spectroscopy - identification of surface peroxo species) Raman spectroscopy was performed on an inVia™ Raman microscope (Renishaw) using a 532 nm excitation laser. For each sample, measurements were performed at five different sample spots. Three scans were acquired at each sample spot and the average was recorded. The acquisition time for each scan was 20 seconds. The spectra were characterized by the main peaks of the support (e.g., 465 cm for CeO2, 475 cm for Cr ... -1 F 2g Peaks were normalized to the mean of the 100 nm peak. Normalized spectra recorded at five different sample spots were averaged.

[0092] (N2 physical adsorption analysis (BET specific surface area)) The specific surface area of ​​the catalytically active materials in particulate form (powder) was determined from N2 adsorption isotherms by the BET method. N2 physical adsorption measurements were carried out on an ASAP 2020 PLUS (Micromeritics Instrument).

[0093] (The number of noble metal atoms normalized to the surface area of ​​the catalytically active material (particle) (N S )(at / cm 2 )) For catalytically active materials in particulate form, the specific surface area (m 2 / g to cm 2 / g) and the amount of precious metal deposited (g converted to at) were used to calculate the monoatomic surface density (the number of precious metal atoms normalized to the surface area of ​​the catalytically active material (N S ) was calculated. If the precious metal is deposited by impregnation techniques, the total amount of precious metal atoms (g) present in the aqueous solution can be used for the calculation if the deposition is quantitative; otherwise, the amount can be obtained from the achieved yield.

[0094] (Calculation of O 1s bond energy) The binding energies of the O 1s level at the surface were calculated using density functional theory (DFT) within the final state approximation by referencing the O 1s signal oxygen in a ceria bulk (2 × 2 × 2) supercell. Details of DFT are given in a later chapter.

[0095] (CO oxidation reaction on catalytically active materials in membrane form) Reactivity measurements were carried out in a high pressure cell (SPECS HPC 20) connected to the main UHV analysis chamber. The catalytically active material was heated by a halogen lamp outside the chamber through a quartz window. The reaction mixture consisted of 10 mbar CO and 50 mbar O2, balanced to 1 bar with He. The gas composition in the reactor was analyzed by leaking gas through a quartz microcapillary into a quadrupole mass spectrometer (QMS, MKS). Starting from room temperature, the temperature of the catalytically active material was increased stepwise in increments of 50 K and CO2 production was monitored by the QMS. In an experiment aimed at assessing the stability of atomically dispersed noble metals in the catalytically active material in the CO oxidation reaction, the sample was heated to 523 K at a rate of 1 K / s and held under reaction conditions for 10 min, after which the sample was cooled to 300 K, evacuated and then transferred to the analysis chamber for post characterization.

[0096] (Infrared Reflection Absorption Spectroscopy (IRAS)) IRAS measurements were carried out on the catalytically active material in film form using a Bruker 66ivs FTIR spectrometer in a UHV chamber housing a "high pressure" cell (reaction volume 1) to expose the sample to a gas mixture at near atmospheric pressure.

[0097] The IRAS spectrum of CO adsorption was measured according to the steps described below: (1) cooling the catalytically active material to 200K in UHV; (2) CO2 = 10 -6 The pressure was then increased to 1000 psi for 100 seconds, and then CO was pumped for 10 -9 evacuating to below mbar; (3) recording an IRAS spectrum; (4) heating the catalytically active material to 500K at a rate of 60K / min in UHV and cooling to 200K; and (5) Repeat steps (2) to (4) twice.

[0098] IRAS measurements were also carried out on the catalytically active material after exposure to a reaction mixture consisting of 1% CO and 5% O2 at 1 bar, balance Ar. The measurements were carried out as follows: (1) exposing a catalytically active material in a reaction cell to a reaction mixture; (2) heating the catalytically active material to 500 K at a rate of 60 K / min and reacting the mixture at 500 K for 5 minutes; (3) cooling the catalytically active material to 300K; (4) Remove the reaction mixture from the reaction cell and -9 applying UHV conditions of 0.5 to 1000 psi (mbar); (5) Recording a spectrum in UHV at 300K without further exposure to CO; (6) increasing the temperature of the catalytically active material to 500K at a heating rate of 60K / min and recording spectra at 320K, 360K, 400K, 440K, 480K and 500K.

[0099] (CO oxidation reaction on catalytically active materials in particle form) The reactivity of catalytically active materials (powder) in CO oxidation reaction was measured in a tubular packed bed reactor. The gas phase composition was analyzed by QMS (Hiden 20). The catalytically active materials were sieved to less than 75 μm and 1 part by weight of catalytically active materials was physically mixed with 4 parts by weight of silica gel. The resulting mixture (5 parts by weight) was then mechanically mixed with 1 part by weight of acid purified SiO2 and loaded into a glass tube reactor. The temperature was increased stepwise to 373K, 383K, 403K, 423K, 443K and 473K in a gas mixture of 1% CO and 20% O2 (He balance) at 1 bar and the CO oxidation reaction rate was measured at steady state for at least 1 hour at each temperature.

[0100] (Alkyne hydrogenation over catalytically active materials in particulate form) The reactivity of catalytically active material in particle form (powder) in alkyne hydrogenation reaction was measured in a tubular packed bed reactor using acetylene as alkyne. The gas phase composition was analyzed by QMS (Hiden 20). The catalytically active material was sieved to less than 75 μm and loaded undiluted into a glass tube reactor. The temperature was increased stepwise to 373, 393, 413, 433, 453 and 473 K at 1 bar in a mixture of 1% C2H2 and 5% H2 (balance Ar) and the steady state rate of alkyne hydrogenation was measured at each temperature for 12 h. The average ethene production rate observed during the 12 h hydrogenation reaction at each temperature was recorded as the hydrogenation rate of acetylene.

[0101] (Pt / CeO2 film sample) (Reference example 1: CeO2(111) membrane support) Experiments were carried out in an ultra-high vacuum (UHV) chamber equipped with a low energy electron diffraction (LEED), an X-ray photoelectron spectroscopy (XPS), and a scanning tunneling microscope (STM), all from SPECS GmbH. Stoichiometrically ordered CeO2(111) films were grown on Ru(0001) single crystals as follows. A Ru(0001) single crystal (9 mm diameter, 1.5 mm thick, from MaTeck GmbH) was mounted on a stainless steel sample holder with a 9 mm diameter hole for heating the sample from the backside using an electron beam from a W filament. Type K thermocouples were spot welded to the ends of the crystal. 10 -6 The Ru(0001) surface was oxidized at 1000 K in 1000 mbar O2. 10 -6 Ce was vapor-deposited onto the oxidized Ru(0001) surface at 90 K under 1 mbar O in an amount equivalent to forming 4 to 5 monolayers (ML) of CeO(111). The temperature of the Ru(0001) was then increased at a rate of 1 K / s and maintained at 673 K during the deposition of an additional CeO layer. -6 The sample was oxidized at 1000 K under mbar of O2. The thickness of the CeO2(111) film was approximately 5 nm. The prepared sample is denoted as "CeO2(111)".

[0102] (Reference example 2: CeO2-red membrane support) The CeO2(111) film was UHV annealed at 1200 K for 5 min to obtain reduced CeO 2-x (111) surface (hereafter referred to as “CeO2-red”) was prepared.

[0103] (Reference Example 3: Preparation of CeO2-step membrane support) A CeO2(111) surface enriched with monoatomic steps (denoted as "CeO2-steps") was prepared following the procedure described in Nat. Commun. 7 (2016) 10801. In particular, this was obtained by depositing 0.3 monolayers (ML) of Ce on a CeO2(111) film and subsequent oxidation at 673 K. This resulted in the formation of islands of small ML heights. This homoepitaxy of CeO2 on CeO2 results in well-arranged samples with a high step density.

[0104] (Reference Example 4: Preparation of CeO2-plasma membrane support) A microwave plasma generator equipped with a commercial plasma source (OSPrey, Oxford Scientific, Figure 1A) was used to generate 7 × 10 -6 Oxygen plasma treatment of CeO2(111) films was carried out by operating under mbar O2 at an anode voltage of 1 kV and an emission current of 0.5 μA. The as-prepared sample is denoted as “CeO2-plasma”.

[0105] (Example 1: Preparation of Pt / CeO2-plasma membrane sample) Pt was deposited on the CeO2 plasma film from Pt rods using an electron beam assisted evaporation system (Omicron EMT3). To minimize metal agglomeration during deposition at room temperature, Pt was intentionally deposited at a low metal flux, i.e., 0.03 ML / min, as determined by a quartz crystal microbalance (McVac). Here, 1.0 ML of Pt corresponds to 1 Pt atom per CeO2(111) surface unit cell, i.e., 7.9 × 10 14 Pt atoms / cm 2During deposition, the sample was biased at the same potential as the Pt rod. The amount of Pt was controlled to be 0.20 ML through the analysis of the Pt 4f signal intensity by XPS. The obtained sample is denoted as "Pt / CeO2-plasma".

[0106] The resulting "Pt / CeO2-plasma" sample was then subjected to UHV annealing. The sample was exposed to UHV and heated to 523 K at a heating rate of 120 K / min, held at 523 K for 5 min under UHV, and then cooled at a cooling rate of 60 K / min. The resulting sample is referred to as "annealed Pt / CeO2-plasma".

[0107] The obtained annealed Pt / CeO2 plasma film catalyst showed the following characteristics. The average diameter of the CeO2 clusters measured by STM was about 1.0 nm. The number of Pt atoms (area density, Ns) on the sample surface calculated from the amount of Pt film (0.2 mL) was 1.6 × 10 14 at / cm 2 The Pt in the catalytically active material measured by XPS 0 , Pt 2+ and Pt 4+ Pt vs. total intensity 2+ The relative intensity of the CeO2 clusters was 100%. The number of CeO2 clusters normalized to the surface area of ​​the CeO2 substrate by STM measurement was 0.15 clusters / nm 2 It was stipulated that:

[0108] (Comparative Example 1: Preparation of Pt / CeO2(111) film sample) In the same manner as in Example 1, Pt was deposited on the CeO2(111) film prepared in Reference Example 1. The resulting sample is referred to as "Pt / CeO2(111)". In the same manner as in Example 1, UHV annealing was applied to Pt / CeO2(111). The resulting sample is referred to as "annealed Pt / CeO2(111)".

[0109] (Comparative Example 2: Preparation of Pt / CeO2-red film sample) In the same manner as in Example 1, Pt was deposited on the CeO2-red film prepared in Reference Example 1. The obtained sample is referred to as "Pt / CeO2-red". In the same manner as in Example 1, UHV annealing was applied to Pt / CeO2(111). The obtained sample is referred to as "annealed Pt / CeO2-red".

[0110] (Comparative Example 3: Preparation of Pt / CeO2-step membrane sample) In the same manner as in Example 1, Pt was deposited on the CeO2-step film prepared in Reference Example 1. The obtained sample is referred to as "Pt / CeO2-step". In the same manner as in Example 1, UHV annealing was applied to Pt / CeO2(111). The obtained sample is referred to as "annealed Pt / CeO2-step".

[0111] (Comparative Example 4: Preparation of Pt / CeO2-sputtered film sample) First, a CeO2 (111) support was prepared by the same method as in Reference Example 1. Next, the CeO2 (111) film was irradiated with 1 keV Ar at 300 K for 5 minutes. + The ceria surface was then roughened by ion bombardment. As determined by XPS, the surface was significantly reduced due to preferential sputtering of the lighter O atoms. -6 The film was exposed to O2 at 100 mbar and 500 K. The resulting substrate is designated as "CeO2-sputtered".

[0112] Next, 0.2 ML of Pt was deposited on the "CeO2-sputtered" support in a manner similar to that described in Example 1. The resulting sample is designated "Pt / CeO2-sputtered". UHV annealing was applied to Pt / CeO2(111) in the same manner as in Example 1. The obtained sample is denoted as "annealed Pt / CeO2 sputtered".

[0113] (Evaluation of Results) The results obtained for the membrane samples are given below.

[0114] Figure 2 shows the Pt 4f XPS spectra obtained for the (annealed) Pt / CeO2 samples of Example 1 and Comparative Examples 1-3, measured before and after the CO oxidation reaction described above at 523 K in a reaction mixture containing 10 mbar CO and 50 mbar O2, balanced to 1 bar with He. To distinguish solely thermal from reaction-induced effects, all samples were annealed in UHV at 523 K prior to reaction. The complete XPS data sets for Pt 4f, Ce 3d and O 1s levels are shown in Figures 3-6.

[0115] First, the results of Comparative Example 1 are described. The as-deposited Pt species in Pt / CeO2(111) were characterized by a binding energy (BE) of 71.8 eV (Figure 3), which suggested the formation of small Pt metal clusters. In the annealed Pt / CeO2(111) sample, the peak shifted to a lower BE (71.4 eV), which suggested the sintering of Pt metal clusters upon UHV annealing. The spectrum obtained after the CO oxidation reaction consisted of several states determined by deconvolution: the 71.1 eV state is associated with larger metal nanoparticles (NPs), suggesting further Pt sintering under the reaction conditions. Two other signals centered at 74.2 and 72.7 eV were assigned to Pt in the 4+ and 2+ oxidation states, respectively.

[0116] Analysis of the Ce 3d and O 1s XPS spectra (FIG. 3) measured on the CeO2(111) substrate according to Reference Example 1 and the Pt / CeO2(111) sample according to Comparative Example 1 showed no significant difference before and after Pt deposition, measured at 300 K. Compared to the Pt / CeO2(111), the annealed Pt / CeO2(111) sample showed a large increase in Ce 3+The relative amount of increased slightly, suggesting ceria reduction of Pt-derived moieties upon annealing at 523 K in UHV. The Ce 3d spectrum was fully restored after the CO oxidation reaction in an O-rich atmosphere. Since the stoichiometric CeO2(111) surface is essentially inert to residual gases in the UHV background at 300 K, the O 1s signal at 529.3 eV did not show any additional states for adsorption (typically hydroxyl and carbonate) before and after Pt deposition, i.e., in the CeO2(111) support and in the Pt / CeO2(111) sample. However, after the CO oxidation reaction, a significant signal appeared at 531.8 eV, which could be attributed to the adventitious CO2 (and possibly water) adsorption on the bare ceria support at "high" pressure.

[0117] As can be seen from FIG. 2, the surface of the CeO2-red membrane support of Reference Example 2 showed a complex (√7×√7)-R19.1° LEED pattern, which was associated with the long-range ordering of O vacancies at the surface. In contrast to the stoichiometric CeO2(111) support of Reference Example 1, this surface reacted easily with traces of water in the UHV background, resulting in an additional weak O 1s signal at 532.0 eV from surface hydroxyls (FIG. 4). In the Pt / CeO2-red sample of Comparative Example 2, more than the Pt metal atoms (BE at 71.6 eV) that constituted small clusters, and some Pt ​​atoms were in the 2+ oxidation state (72.8 eV). However, in the annealed Pt / CeO2-red sample, Pt was not oxidized during the UHV annealing treatment. 2+ The signal disappears, while the Pt 0 The signal increased in intensity, and the spectrum became virtually identical to that observed for a stoichiometric CeO2 surface (Figure 2). After the CO oxidation reaction, the Pt in the annealed Pt / CeO2-red sample was almost exclusively Pt 2+ state (72.8 eV), Pt 4+ (74.2 eV) is somewhat smaller, and Pt 0The state shifted to 71.1 eV. Again, the results can be explained by the formation of relatively large Pt nanoparticles that underwent oxidation. At the same time, the ceria surface was completely oxidized due to the O2-rich mixture used in the CO oxidation reaction (Ce 3+ was not detected) (Figure 4).

[0118] Returning to Comparative Example 3, in the as-deposited Pt / CeO2-step sample, Pt atoms were partially in the 2+ and metallic states (BEs of 72.8 and 71.9 eV, respectively, see FIG. 5). In contrast to Comparative Example 1, after UHV annealing, in the annealed Pt / CeO2-step sample, Pt 2+ The species was thermally stable and remained on the surface together with small metal clusters that sintered upon annealing (the corresponding BE shifted from 71.9 to 71.7 eV). After the CO oxidation reaction, metallic Pt atoms were not observed on the surface, and Pt 2+ and Pt 4+ It contained only seeds.

[0119] As mentioned above, in Comparative Examples 1 to 3, Pt NPs (nanoparticles) were always formed during UHV annealing of the Pt deposits. A certain amount of thermally stable Pt was observed in the annealed Pt / CeO2 step samples. 2+ The species can be explained by the strong adsorption of Pt single atoms at the step edges. Upon exposure to a CO oxidizing atmosphere, the metal clusters were oxidized, which gave rise to 4+ and 2+ states, the proportion of which depended on the initial particle size. 4+ and Pt 2+ The formation of the species is well documented in the literature. It is generally characterized as PtO2 / PtO clusters or thin PtO on large Pt nanoparticles. x This is caused by the oxide film.

[0120] Finally, Fig. 2 shows the LEED pattern obtained for the CeO2-plasma film support according to Example 4. This sample was substantially different from the samples of Examples 1 to 3 in that no long-range ordering was observed. As can be seen from the Pt 4f SPX spectrum of the Pt / CeO2-plasma sample, the Pt starting from the "as-deposited" sample remained exclusively in the 2+ state even during the CO oxidation reaction at near atmospheric pressure (Figs. 2 and 6).

[0121] To clarify the origin of the exceptional stability of Pt on the annealed CeO2-plasma surface, the film morphology was investigated using STM. STM images (Fig. 7b-c) reveal the formation of randomly distributed CeO2 clusters with diameters of about 1.0 nm on the surface of the CeO2-plasma substrate of Reference Example 4. The initial film morphology showing terraces separated by monoatomic steps is still visible. Such CeO2 clusters were not observed on the CeO2(111) substrate of Reference Example 1 (Fig. 7a). The STM results also explain the lack of long-range order observed by LEED (see Fig. 2).

[0122] Importantly, the O 1s XPS spectra of the CeO2-plasma support and Pt / CeO2-plasma samples (Fig. 7e) reveal a pronounced shoulder at 530.8 eV, which cannot be attributed to adventitious hydroxyls and / or carbonates, and shows a significantly higher BE of about 531.8 eV (Figs. 3-5). The signal shifted by 1.6 eV relative to the main peak at 529.2 eV and increased with increasing plasma exposure time. Also, there was a gain in signal intensity when measured with more surface-sensitive grazing radiation. All these findings point to the formation of new oxygen species, which were not present in the other CeO2 film supports used in Comparative Examples 1-3. Based on DFT calculations of atomic O adsorption on the stoichiometric CeO2(111) surface and the corresponding BE shift of the O 1s level (Fig. 7f, see details below), the signal at 530.8 eV is likely due to surface peroxides, O2 2-was attributed to (Figs. 8 to 9). Table 1 shows the PBE+U core level binding energies (in eV) for oxygen species on the CeO2 surface at various peroxide coverages. The values ​​shown correspond to the average results in each case, since all oxygen atoms located in the surface layer are sampled. The values ​​are always referenced to the simulated O 1s signal of oxygen atoms in a ceria bulk (2x2x2) supercell. For 0.5 ML, two different geometric arrangements of peroxide groups are possible (shown as "diag" and "row" in Fig. 9).

[0123] [Table 1] To identify the Pt species formed on the CeO2 plasma films, IRA spectroscopy was used using CO as a probe molecule. We consider the CO IRAS results obtained on the (annealed) Pt / CeO2-plasma sample of Example 1 and the (annealed) Pt / CeO2(111) sample of Comparative Example 1. It was observed that the bare ceria surface does not adsorb CO under the investigated conditions.

[0124] In the case of the Pt / CeO2(111) sample of Comparative Example 1, the adsorption (10 -6 mbar) (Figure 10a) at 2087 and 2024 cm -1 The IRAS bands around 2060 cm -1 The former two signals disappeared after UHV annealing at 500 K and subsequent re-exposure to CO, but a weaker band appeared as a shoulder near 2060 cm -1 The bands at 2087 and 2024 cm increased in intensity. The latter can be attributed to the stretching vibrations of CO adsorbed on the low-coordinated sites on the metallic Pt nanoparticles located at the step edges, as previously shown by STM. Thus, the bands at 2087 and 2024 cm observed for the Pt / CeO2(111) sample -1The band is assigned to CO adsorbed on Pt clusters and aggregates with unfavourable structures, since its formation is influenced by the limited diffusivity of surface adatoms at these relatively low temperatures.

[0125] In contrast, in the case of the Pt / CeO2-plasma sample of Example 1, CO adsorbed on the Pt species formed on the CeO2-plasma surface was observed at 2104 cm -1 In the case of CO adsorbed on a sample heated to 500 K in UHV, the band becomes much lower and appears in the red (2095 cm -1 ) at 100 K. The spectrum was fully reproducible after several thermal flashes up to 500 K, suggesting a good thermal stability of the Pt species and in perfect agreement with the XPS data. The IR bands were very similar to those reported in the literature for powdered Pt SAC verified by high-resolution electron microscopy. However, after a thermal flash up to 700 K the bands disappeared, suggesting that the Pt atoms were no longer accessible to CO. It should be noted, however, that IRAS spectra on metal-supported oxide films obey selection rules such that only vibrations associated with dipole changes perpendicular to the metal surface can be detected. Thus, CO molecules oriented parallel to the Ru(0001) surface underneath the ceria film are not visible in the IRAS spectrum.

[0126] These two systems (Example 1 and Comparative Example 1) were also investigated in IRAS after exposure to 1 bar reaction mixture containing 1% CO and 5% O2 (Ar balance) in a "high pressure" cell. After 5 min reaction at 500 K and cooling the sample to room temperature, the cell was pumped down and IRAS spectra were recorded at 300 K in UHV without additional CO exposure. Interestingly, the spectra show a peak at approximately 2110 cm for both systems. -1 (2070 cm) observed on annealed Pt / CeO2(111) -1The weak and broad band at 2113 cm can be attributed to traces of CO at the edges of the metallic Pt nanoparticles (see above). However, when the sample was slowly heated to 500 K, the spectrum showed a different behavior. For the annealed Pt / CeO2(111) of Comparative Example 1 (see Figure 10a), the band at 2113 cm -1 The bands gradually shift to lower wavenumbers (10 cm -1 The integrated intensity of the CO peaks decreased slightly, indicating partial desorption of CO. Such a spectral change and its peak position are characteristic of CO adsorbed on the O-precoated Pt surface and can be explained in relation to the dipole-dipole interactions between adjacent CO molecules adsorbed on the surface where some of the Pt nanoparticles formed initially before the reaction were oxidized. The formation of relatively large metallic Pt nanoparticles on CeO2(111) can also explain the high signal intensity of the IRAS band due to the image charge effect. In contrast, in the case of the annealed Pt / CeO2 plasma in Example 1, the 2110 cm observed on the annealed Pt / CeO2 plasma surface was significantly higher than that of the annealed Pt / CeO2 plasma. -1 A much weaker band at 1000 K remained constant during sample heating up to 500 K (Figure 10b). This band disappeared completely upon heating to 700 K and was not observable upon exposure to CO at room temperature, but regenerated after a second CO oxidation reaction (not shown). Based on these comparative XPS and IRAS studies, it can be concluded that Pt deposited on the plasma-treated CeO2 surface forms a single atom, which remains stable under the reaction atmosphere, even though its coordination to the ceria surface may be affected by the CO oxidation reaction.

[0127] Based on the structural characterization of the CeO2 plasma surface by LEED and STM, it is suggested that the enhanced stability of Pt is due to the surface roughening, which suppresses the diffusivity of Pt adatoms and thus their aggregation. To test this idea, we irradiated the ordered CeO2(111) film with 1 keV Ar at 300 K for 5 min. + A rough CeO2 surface was formed by bombarding with ions. The resulting "CeO2-sputtered" support was used to prepare the (annealed) Pt / CeO2-sputtered sample of Comparative Example 4.

[0128] As can be seen from the Pt 4f XPS spectrum (Fig. 11a), the Pt in the Pt / CeO2-sputtered sample of Comparative Example 4 is mainly in the 2+ state, but a significant amount of Pt in the metallic state (71.5 eV) was also observed, probably as Pt nanoparticles. As shown in Fig. 11b, a substantially higher intensity was observed for the signal at 530.8 eV in the O 1s spectrum of the Pt / CeO2-plasma sample of Example 1 compared to the Pt / CeO2-sputtered sample of Comparative Example 4. This result suggests that the plasma treatment of the CeO2 support formed more "O-rich" sites and stabilized the Pt monoatoms.

[0129] Finally, the activity of the annealed Pt / CeO2-plasma sample of Example 1 in the CO oxidation reaction is compared with that of the annealed Pt / CeO2(111) sample of Comparative Example 1. Steady-state CO2 production rates were measured for the catalysts of Example 1 and Comparative Example 1 at different sample temperatures that were gradually increased in a high-pressure cell filled with 10 mbar CO and 50 mbar O2 balanced to 1 bar with He. The results are shown in Figure 12a. As can be seen, the heat-treated Pt / CeO2-plasma sample of Example 1 showed a higher CO2 production rate than the heat-treated Pt / CeO2(111) sample of Comparative Example 1.

[0130] (Pt / CeO2 powder catalyst) (Reference Example 5: Preparation of untreated CeO2 powder support) High surface area (50m) nanomaterials from US Research Nanomaterials (stock no. US3037) 2 / g) CeO2 powder was purchased and used as is.

[0131] Comparative Example 5: Preparation of Untreated Pt / CeO2 Powder Catalyst Powdered Pt / CeO2 samples were synthesized by the strong electrostatic adsorption (SEA) method. High purity (99.995%) tetraammineplatinum(II) nitrate (TAPN) (Sigma Aldrich No. 482293) was used as the Pt precursor, and ammonium hydroxide (28% to 30% aqueous solution) was purchased from ACROS Organics. The raw Pt / CeO2 powder catalyst was obtained by the following steps: 1) 1 g of ceria was ground and sieved to a powder finer than 75 μm, which was then added to a solution of deionized water mixed with NH 4 OH at pH 9 to prepare a support solution. 2) 10 mg of TAPN was dissolved in 5 mL of deionized water to obtain an aqueous TAPN solution. 300 μL of the resulting solution was added to 25 mL of NH4OH solution with a pH of 9. The resulting solution (25.3 mL) was slowly added to the support solution via a burette. This process took approximately 3.5 hours. 3) The solution obtained in step 2) above was dried in a rotary vacuum evaporator (343K, 110 rpm). 4) In a muffle furnace, the dried catalyst was calcined in air at 723 K for 4 h at a heating rate of 10 K / min, and then cooled to room temperature.

[0132] Example 2: Preparation of plasma-treated Pt / CeO2-powder catalyst First, an untreated Pt / CeO2 powder catalyst was prepared in the same manner as in Comparative Example 5. Next, this untreated Pt / CeO2 powder catalyst was subjected to O2 plasma treatment as follows to obtain a plasma-treated Pt / CeO2 powder sample.

[0133] O2 plasma treatment was carried out in an apparatus consisting of a fritted glass tube, a funnel-shaped glass apparatus, a mechanical pump, a high-frequency plasma generator, and a high-voltage power supply. A schematic diagram of the apparatus configuration for O2 plasma treatment is shown in Figure 1B. The glass tube was covered with a Cu mesh connected to a high-voltage power supply. The frit can hold the calcined powder with gas blowing out from the bottom. The funnel-shaped glass apparatus connected to the top of the tube, and the other three outlets of the funnel-shaped glass apparatus were connected to a pressure gauge, a mechanical pump, and a tungsten rod for grounding. The tungsten rod extends to the bottom of the glass tube, and a uniformly distributed plasma is achieved.

[0134] The plasma was generated by a 20 to 60 kHz high voltage power supply (PVM500). The peak voltage was measured by an oscilloscope with a high voltage probe, and the plasma power was the product of the square root of the mean square (RMS) voltage and the RMS current measured by a multimeter. The power and frequency output of the powder feed were adjusted until a plasma with the desired power was formed.

[0135] The conditions for O2 plasma treatment were as follows: 1) Untreated Pt / CeO2 powder catalyst was introduced into a glass tube (100 to 300 mg) and the tube was evacuated to less than 20 mPa. 2) Oxygen (O2) was flowed from the bottom of the tube at an O2 flow rate of 20 mL / min set by a mass flow controller (MFC). 3) In the turbulent flow, the powder sample began to float. 4) The plasma was ignited. The power output and frequency of the power supply were adjusted to achieve a target power of 200W. 5) The plasma treatment took one hour.

[0136] (Reference Example 6: Preparation of plasma-treated CeO2 powder support) The CeO2 nanoparticles of Reference Example 5 were subjected to O2 plasma treatment in the same manner as in Example 2 to prepare a plasma-treated CeO2 powder support.

[0137] (Examples 3 and 4) First, as shown in Table 2 below, an untreated Pt / CeO2 powder catalyst was prepared in the same manner as in Comparative Example 5, except that the amount of TAPN dissolved in 5 mL of deionized water was changed in step 2). Next, an O2 plasma treatment was performed on the untreated Pt / CeO2 powder catalyst in the same manner as in Example 2, to prepare a plasma-treated Pt / CeO2 powder catalyst.

[0138] (Comparative Examples 6 and 7) Untreated Pt / CeO2 powder catalyst was prepared in the same manner as described for Comparative Example 5, except that the amount of TAPN solution added to the 25 mL NH4OH solution in step 2) was changed as shown in Table 2 below. In Example 4 and Comparative Example 7, an aqueous TAPN solution was prepared by dissolving 20 mg of TAPN in 10 mL of deionized water.

[0139] [Table 2] Due to the impregnation preparation method used, it can be assumed that all the deposited Pt atoms are located on the surface of the CeO2 support and in CeO2 clusters in the prepared catalytically active material. Table 3 shows the surface density Ns of Pt atoms in the catalytically active material.

[0140] [Table 3] (Evaluation of Results) 13a shows the CO2 production rates measured for the Pt / CeO2 powder samples of Example 2 and Comparative Example 5. As can be seen, the plasma-treated Pt / CeO2 powder catalyst of Example 2 exhibited a higher CO2 production rate than the untreated Pt / CeO2 catalyst of Comparative Example 5.

[0141] 13b and 13c show STEM images of the plasma-treated Pt / CeO2 catalyst of Example 2 recorded before and after the CO oxidation reaction at 523 K. Single Pt atoms were observed on the plasma-treated sample before and after the CO oxidation reaction.

[0142] FIG. 14 shows the Pt 4f XPS spectra of the Pt / CeO2 powder catalysts of Examples 2 to 4 (FIG. 14a) and Comparative Examples 5 to 7 (FIG. 14b) measured after the CO oxidation reaction. At Pt loadings of 0.5 wt % or more, the Pt 4+ As indicated by the peaks, PtO2 clusters were observed in both the untreated and plasma-treated Pt / CeO2 powder samples. 4+ The content of species was lower in the plasma treated Pt / CeO2 catalyst (Fig. 14a) compared to the untreated Pt / CeO2 catalyst (Fig. 14b) representing the conventional synthesis, suggesting a better atomic distribution of Pt.

[0143] FIG. 15 shows STEM images of plasma-treated Pt / CeO2 catalysts of Examples 3 and 4 (FIGS. 15a and 15c) and untreated Pt / CeO2 catalysts of Comparative Examples 6 and 7 (FIGS. 15b and 15d) after exposure to CO oxidation reaction. Untreated Pt / CeO2 catalysts show fewer Pt single atoms, which favors the formation of small oxide clusters (PtO2). Compared to the plasma-treated Pt / CeO2 samples, it was more difficult to detect Pt on CeO2 in the untreated Pt / CeO2 samples measured after CO oxidation. Without being bound by theory, this is presumed to be due to the formation of PtO2 clusters in the untreated Pt / CeO2 catalysts (consistent with XPS). In STEM, more Pt single atoms were observed in the plasma-treated Pt / CeO2 samples, suggesting a better distribution of Pt atoms, which is consistent with the XPS results.

[0144] FIG. 16a shows the Raman spectra of the untreated CeO2 support of Reference Example 5 and the plasma-treated CeO2 support of Reference Example 6. The 465 cm -1 The Raman bands of bulk CeO2 are 2g The plasma-treated CeO2 support exhibited a 831 cm -1The CeO2 support showed a Raman band at 831 cm, whereas no such band was observed in the untreated CeO2 support. -1 The bands in the figure are surface peroxo (O2 2- ) species.

[0145] FIG. 16b shows the Raman spectra of the untreated Pt / CeO2 catalyst of Comparative Example 4 and the plasma-treated Pt / CeO2 catalyst of Example 2. Both Raman spectra show F 2g 465cm due to mode -1 The results are normalized to the main band at 831 cm. The plasma-treated Pt / CeO2 catalyst has a significantly higher peak at 831 cm compared to the untreated Pt / CeO2 catalyst. -1 The O2 plasma treatment of the Pt / CeO2 catalyst enhanced the formation of surface peroxo species. FIG. 17 shows the ethene production rates measured for the Pt / CeO2 powder samples of Example 2 and Comparative Example 5. As can be seen, the plasma-treated Pt / CeO2 powder catalyst of Example 2 exhibited a higher ethene production rate than the untreated (calcined) Pt / CeO2 powder catalyst of Comparative Example 5.

[0146] (Pt / TiO2 film sample) (Reference Example 7: Preparation of TiO2(110) support) TiO2(110) single crystals were purchased from SurfaceNet. The surface of the TiO2(110) single crystal was cleaned by cycles of ion sputtering-oxygen annealing, which were repeated until no contamination was detected by XPS, to obtain clean TiO2(110) single crystals. This method is well known and described in the literature (Diebold et al., Surface Science, 1995, 331-333 (PART B), 845-854).

[0147] (Reference Example 8: Preparation of TiO2-plasma film support) The clean TiO2(110) single crystal of Reference Example 7 was subjected to oxygen plasma treatment in the same manner as in Reference Example 4. The obtained sample is referred to as "TiO2-plasma".

[0148] (Example 5: Preparation of Pt / TiO2-plasma film sample) A Pt / TiO2-plasma sample was obtained in the same manner as in Example 1, except that a Pt film was formed on the TiO2-plasma film support.

[0149] (Comparative Example 8: Preparation of Pt / TiO2(110) film sample) A Pt / TiO2(110) sample was obtained in the same manner as in Example 5, except that Pt was deposited on a clean TiO2(110) film support, and therefore no plasma treatment was performed.

[0150] (Evaluation of Results) FIG. 18 shows the Pt 4f XPS spectra obtained for the Pt / TiO2 samples of Example 5 and Comparative Example 8. The Pt in the Pt / TiO2-plasma sample was almost exclusively in the 2+ oxidation state, as indicated by the XPS signal at 72.8 eV. This suggests that the Pt in the Pt / TiO2-plasma sample exists as a single atom. The Pt / TiO2 sample showed a major signal at 71.6 eV, which is the Pt 0 This suggests the formation of metallic Pt nanoparticles or clusters.

[0151] (Theoretical model research) The studies described in this application describe mechanistic considerations regarding one embodiment of the present invention, and are not to be understood as describing the actual situation or as limiting the scope of the invention, but rather serve to illustrate the invention.

[0152] (Reference example 9) (Calculation method) Calculations were performed with the Vienna Ab initio Simulation Package (VASP, version 5.4.4) using the generalized gradient function by Perdew, Burke and Ernzerhof (PBE). Core electrons were treated within the projector augmented wave (PAW) method and valence electrons were expanded to plane waves with a basis set cutoff of 500 eV. Additional Hubbard corrections (DFT+U) were applied to the Ce(4f) bands with an on-site effective U parameter of 4.5 eV according to Dudarev et al. (Phys. Rev. B, 1998, 57, 1505-1509).

[0153] Optimization of bulk ceria yielded a theoretical lattice parameter of 5.491 Å. (111), (110), and (100) surfaces were modeled using (2 × 2) slabs. Stepped surfaces were conveniently prepared as (1 × 2) supercells. At least 10 Å of vacuum was applied on top of the slabs. The bottom layers of the slabs (about half the total number) were kept fixed in their optimized bulk positions, while the top layers were allowed to relax. A dipole correction along the surface normal was applied throughout; about 0.025 Å. -1 Sampling of the Brillouin zone was performed using a G-centered k-point lattice with a reciprocal lattice spacing of 100 nm. Convergence of atomic positions was assumed when the absolute force acting on each atom dropped below 0.15 eV / Å. Spin polarization was taken into account when necessary. Peroxide formation and adsorption energies of Pt and CO were obtained by stepwise structural relaxation starting from a previously optimized untreated surface. For the ceria NP / slab composite model, we verified the CeO2 stoichiometry using initial octahedral nanoparticles, following the well-known Wulff structure, and applying several cuts. The resulting ceria nanoislands were fixed on a 9-atom-layer CeO2(111)-(7×7) slab. The entire system consisted of 178 cerium atoms and 356 oxygen atoms (film-Ce 147 O 294 ;NP-Ce 31 O 62 ), 27.18×27.18×7.94Å 3Due to the large cell size, the optimization was performed at the gamma point.

[0154] The evaluation of the CO vibrational frequencies was carried out by applying small stepwise displacements of the relevant platinum, carbon and oxygen atoms (VASP-tag NFREE=2). Due to the high computational cost, a modified version of the NP / slab composite system was used, keeping only the surface layer of the underlying slab and Pt fixed. The reference calculations were performed with the deviation caused by this approximation being 10 cm -1 The approach was validated by showing that the σ-axis remains below σ-axis, validating the approach. Also, for extended low index surfaces, higher accuracy was applied by setting the VASP tag PREC to "Accurate". Finally, all frequencies were scaled by reference to the theoretical and experimental values ​​for molecular CO (see Table 4). Table 4 shows the results for Pt adsorption on extended low index ceria surfaces (referenced against gaseous monoatomic Pt), CO adsorption on monoatomic Pt, and the corresponding CO vibrational frequencies (in cm). -1 ) are shown. The calculated vibrational frequencies are the experimental values ​​obtained for CO in the gas phase (2143 cm -1 ) and theoretical value (2125cm -1 ) was scaled using a scaling factor of 1.008.

[0155] [Table 4] The plasma was modeled as isolated oxygen atoms (radicals). The binding energy of the O 1s level at the surface was calculated within the final state approximation and referenced to the O 1s signal of oxygen in a ceria bulk (2 × 2 × 2) supercell.

[0156] (Consider) To understand the rationale behind the formation of ceria NPs observed by STM (see Figures 7a-7c), a thermodynamic model was considered under the assumption that the material forming the ceria NPs originates from the top CeO2(111) layer of the sample (Figure 19). As a result, the ceria film thins, while the total number of ceria formula units remains constant during the reconstruction (Ce atoms are not sputtered by the relatively light O atoms in the plasma). The ceria NPs are approximated as hemispheres that grow overlapping with the underlying film, and surface energies calculated for different peroxo-covered extended surfaces (Tables 5-9), as well as step and corner energies using calculations for high Miller index surfaces (Tables 10-11), are used. Depending on the input parameters, the ceria NPs were between 3 and 11 nm in diameter (Figure 20), i.e., larger than those observed experimentally. Nevertheless, these thermodynamic considerations demonstrate that oxygen plasma, in addition to the assumed collisional effect of energetic O atoms in the plasma, supports the surface reconstruction and the formation of ceria NPs on the initially flat film. Although the increase in surface area resulted in more local surface structures and stabilized oxygen radicals via peroxo groups, at the same time, the exposure of other facets than (111) on the ceria NPs was accompanied by more exothermic reaction energy for the formation of peroxides.

[0157] [Table 5]

[0158] [Table 6]

[0159] [Table 7]

[0160] [Table 8]

[0161] [Table 9]

[0162] [Table 10]

[0163] [Table 11] Not surprisingly, the peroxo species influenced Pt adsorption on the CeO2 surface (Table 12 and Figure 21). Compared to pristine CeO2(111), Pt atoms were bound to the peroxo-covered (111) surface by 1–2 eV stronger depending on the peroxide coverage. On the (100) surface, the peroxo species may weaken the Pt bond, while on the (110) surface the effect is smaller (energy gain is about 0.6 eV on average). Among the surfaces studied, the strongest Pt adsorption was observed for the (100)-4O coordination environment. Interestingly, the presence of peroxo groups did not show any beneficial effect on Pt binding at this site. Pt adsorption on stepped surfaces was also evaluated (Figure 22). Square planar 4O-coordinated environments, especially the (210) and (310) surfaces, could again provide sites for strongly exothermic Pt adsorption (Table 12), but these stepped surfaces exhibited fairly high surface energies and were therefore thermodynamically unstable. Table 13 shows the adsorption energies (in eV) of a single Pt atom adsorbed on the most stable structures on clean peroxide-covered CeO2 surfaces as a function of peroxide coverage (1 ML corresponds to one peroxo group per (1 × 1) surface unit cell). For the 0.5 ML coverage of the (2 × 2) slab used in the calculations, the two peroxo groups allow two non-equivalent geometric configurations: 1) along a unit vector (labeled "r" = row direction) and 2) diagonal to the unit vector ("d" = diagonal). Energies are referenced to the corresponding ceria surface and to the Pt bulk. Negative values ​​indicate exothermic adsorption and unfavorable Pt aggregation (Pt-Pt bond formation).

[0164] [Table 12]

[0165] [Table 13] Next, we evaluated the interaction of Pt single atoms with ceria NPs formed on the CeO2(111) surface, as shown by STM. For this purpose, a model system consisting of a ceria cluster fixed on an extended CeO2(111)-(7 × 7) slab was constructed. The particle size was adapted to the experimentally measured value (i.e., about 1.0 nm, see Fig. 7) and the whole structure was optimized accordingly by DFT (Fig. 23a, center). Apparently new Pt adsorption sites were formed at the interface between the NPs and the surrounding (111) terraces. The calculated adsorption energies (E ads The adsorption potential of Pt (E ads (Pt) = -1.76 eV). Depending on their location on the ceria NP, the coordination environments of the adsorbed Pt atoms were chemically different from those of their symmetrically equivalent counterparts on the extended ceria surface. In particular, at the (100)-4O site, the difference reached 0.9 eV (i.e., -1.76 vs. -0.85 eV on the NP apex and the corresponding extended surface, respectively).

[0166] The NP / terrace boundaries and square planar "nanopocket" Pt binding sites of this system for CO adsorption were also evaluated (Figure 23b, Figure 24). CO did not adsorb to Pt at the (100)-4O site (E ads (CO) = 0.11 eV), but CO adsorption was exothermic in the case of Pt at the NP / CeO2(111) interface (E ads(CO) = -0.86 eV). However, at this site, the CO molecule is oriented almost parallel to the metal support surface and is therefore not visible to IRAS due to the metal selectivity rules mentioned above. Both these findings can explain the very low intensity of the IRAS bands at the "as-deposited" Pt / CeO2-plasma surface compared to the results observed for the Pt / CeO2(111) system (Fig. 10). Regarding the latter, calculations performed for Pt adatoms on an untreated CeO2(111) surface give E ads (CO) = -2.14 eV and 2093 cm -1 This gives a CO frequency of 2087 cm, which is closer to the observed CO frequency of 2087 cm on the “as-deposited” Pt / CeO2(111) sample. -1 For Pt adsorbed on 0.25 and 0.5 ML of peroxo-covered CeO2(111) surfaces, the CO binding energies increase to -2.33 and -2.62 eV, and the CO frequencies are 2081 and 2080 cm, respectively. -1 Nevertheless, the 2104 cm observed in the Pt / CeO2 sample -1 The IRAS bands at can be due to single Pt atoms adsorbed on the bare and / or peroxo-coated CeO2(111) surfaces. Upon UHV annealing at 500 K, these atoms presumably migrate to the more strongly bound boundary and nanopocket sites, where they weakly adsorb CO, resulting in a significant decrease in signal intensity, as shown in Fig. 10b.

[0167] In an attempt to identify the nature of the strongly bound CO adsorbates remaining on the Pt / CeO2-plasma surface after the reaction, several structures were calculated derived from the Pt / nanopocket site by the sequential removal of O atoms from the Pt-4O coordination as a result of the reaction with CO. The resulting structures, shown as Pt-3O and Pt-2O in Fig. 23b, reveal exothermic CO adsorption with energies reaching -2.00 eV and -0.82 eV, respectively. Thus, the Pt-3O structure is recognized as a possible candidate for the CO observed by IRAS on the reacted Pt / CeO2-plasma sample.

[0168] Based on the aforementioned observations, the overall effect of plasma treatment on the structure of the Pt / CeO2(111) surface is rationalized as shown in Figure 25. It is hypothesized that plasma treatment results in two modifications of the ceria surface: 1) morphological modification as evident from the pronounced nanostructuring resulting in the formation of ceria nanoparticles; and 2) chemical modification via the formation of surface peroxides. During Pt deposition, metal atoms can be directly attached to the ceria NPs or adsorbed on the intermediate peroxo-covered CeO2(111) surface. Here, they form isolated and strongly bound complexes with the surface peroxide groups. This is in contrast to the untreated CeO2(111) film surface, where the Pt atoms diffuse across the surface and agglomerate into Pt nanoparticles. With increasing temperature, the peroxo-trapped Pt atoms on the (111) terraces can further migrate to numerous ceria NPs around the particle / terrace boundaries and nanopockets, where they can occupy sites. Therefore, the peroxide-covered CeO2(111) surface can, firstly, prevent the aggregation of Pt during film formation and, secondly, act as a reservoir for Pt monoatoms on the ceria NPs. As a result, the morphological and chemical modifications of the ceria surface, as well as their synergistic interactions, can be beneficial in achieving a high density of stable Pt monoatoms.

Claims

1. A catalytically active material comprising: A support comprising a metal oxide; a noble metal atomically dispersed on the surface of said support; having The metal oxide is TiO 2 , CEO 2 , ZnO, SnO 2 , Ga 2 O 3 , In 2 O 3 , ZrO 2 , and Fe 2 O 3 is selected from the noble metal is selected from Pt, Pd, Rh, and Au; The catalytically active material is 2 2. A catalytically active material obtainable by a process comprising the step of a non-thermal plasma treatment in the presence of

2. The number of precious metal atoms normalized to the surface area of ​​the catalytically active material is 3.0×10 12 at / cm 2 From 8.0×10 14 at / cm 2 , preferably 3.0 x 10 12 at / cm 2 From 4.0×10 14 at / cm 2 , more preferably 6.0×10 12 at / cm 2 From 2.0×10 14 at / cm 2 2. The catalytically active material of claim 1, wherein

3. the relative intensity of the noble metal in oxidation state X relative to the total intensity of the noble metal in all oxidation states in the catalytically active material, as measured by X-ray photoelectron spectroscopy, is 50% or more, preferably 75% or more; 2. The catalytically active material of claim 1, wherein for Pt and Pd, X is 2+, and for Rh and Au, X is 3+.

4. The infrared absorption spectrum measured for the catalytically active material has a peak at 2085 cm -1 From 2120cm -1 and exhibits an absorption band in the range of: (1) 1 bar, 1% CO and 5% O balanced with Ar 2 exposing said catalytically active material in a reaction cell to a reaction mixture comprising (2) heating the catalytically active material to 500 K at a rate of 60 K / min and reacting the mixture at 1 bar and 500 K for 5 min; (3) cooling the reaction mixture and the catalytically active material to 300K; (4) removing the reaction mixture from the reaction cell; -9 Applying ultra-high vacuum conditions of less than mbar; (5) Recording spectra under ultra-high vacuum at 300 K without additional exposure to CO; (6) increasing the temperature to 500K at a rate of 60K / min and recording spectra at 320K, 360K, 400K, 440K, 480K and 500K; and (7) Comparing the absorption maxima in the spectra recorded at each temperature.

2. The catalytically active material of claim 1, wherein the thermal conductivity of the catalytically active material is not changed by heating the catalytically active material from 300K to 500K, as measured by .

5. The metal oxide and the precious metal are the following combination of materials: The metal oxide is TiO 2 and CeO 2 and The noble metal is selected from Pt and Pd. is selected from The metal oxide is CeO 2 2. The catalytically active material according to claim 1, wherein the noble metal is preferably Pt.

6. 2. The catalytically active material according to claim 1, wherein the support is in the form of particles, for example a powder.

7. 7. The catalytically active material of claim 6, wherein the support is composed of the metal oxide.

8. The support has an average particle size of 10 nm to 50 nm as measured by scanning transmission electron microscopy, and is preferably CeO 2 7. The catalytically active material of claim 6 which is a powder support.

9. 7. The catalytically active material of claim 6, wherein the catalytically active material consists of the support and the precious metal.

10. 10. The catalytically active material of claim 1, wherein the support is in the form of a membrane.

11. The support includes a substrate and a cluster supported on the substrate; the substrate and the clusters comprise the same metal oxide; 11. The catalytically active material according to claim 10, wherein the average diameter of the clusters is less than or equal to 2.0 nm, preferably less than or equal to 1.5 nm, as determined by scanning tunnelling microscopy.

12. 12. The catalytically active material of claim 11, wherein the substrate and the clusters are composed of the same metal oxide.

13. CO to CO 2 Use of the catalytically active material according to claim 1 in the catalytic oxidation of The catalytically active material is preferably CO and O 2 is used to react in the presence of said catalytically active material at a pressure of 0.8 to 2.0 bar and a reaction temperature of 323 K to 573 K, The content of CO in the mixed gas is 5% by volume or less, O in the mixed gas 2 The content is 2% by volume or more and 25% by volume or less, CO / O 2 The molar ratio used is preferably 2.0 or less.

14. 2. Use of the catalytically active material according to claim 1 in the catalytic hydrogenation of alkynes, The catalytically active material is preferably Alkynes and H 2 is reacted in the presence of said catalytically active material at a pressure of 0.8 to 2.0 bar and at a temperature of 323 K to 573 K, The content of the alkyne in the mixed gas is 10% by volume or less, H in the mixed gas 2 the molar ratio of the alkyne to is less than or equal to 1; The alkyne is preferably 2 ~C 5 More preferably, the alkyne is C 2 ~C 3 is an alkyne, used.

15. A method for producing the catalytically active material of claim 6, comprising the steps of: (1) providing a precursor of said catalytically active material having a support in the form of particles comprising a metal oxide and a precious metal on a surface of said support; (2) O 2 calcining the precursor for the catalytically active material in the presence of (3) O 2 performing a non-thermal plasma treatment of the calcined precursor for the catalytically active material in the presence of The method comprising:

16. The step (1) includes the following steps: (1a) depositing a precious metal onto the support, preferably from an aqueous solution of a salt of the precious metal, the support preferably consisting of an oxide of the metal; and (1b) co-precipitating the precious metal and the metal oxide from an aqueous solution containing salts of the precious metal and the metal oxide; 16. The method of claim 15, wherein said compound is selected from the group consisting of

17. The non-thermal plasma treatment is carried out at a pressure of 20 mbar or less and at 5 vol% or more of O 2 The method of claim 15, wherein the method is carried out content-wise.

18. A method for producing a catalytically active material according to any one of claims 10 to 12, selected from methods A and B, comprising the steps of: Method A is (1) providing a metal oxide membrane support; (2) O 2 performing a non-thermal plasma treatment in the presence of to obtain a plasma-treated metal oxide membrane support; and (3) depositing a noble metal on the plasma-treated metal oxide film support in the gas phase, preferably by physical vapor deposition of the noble metal atoms; Including, Method B is (1) providing a metal oxide membrane support; (2) depositing a precious metal onto the metal oxide membrane support from a solution containing the precious metal; (3) O 2 performing a non-thermal plasma treatment in the presence of Including, The non-thermal plasma treatment is preferably performed by O 2 1×10 -6 mbar to 1×10 -5 The method is carried out at a pressure of 10 ... mbar.

Citation Information

Patent Citations

  • Catalyst for oxidation of co to co2, its reaction and application

    JP1994219721A

  • Method for promoting low-temperature oxidation reaction using noble metal nanoparticle-carrying metal oxide catalyst

    JP2008049280A

  • RF non-thermal plasma techniques for catalyst development to improve process efficiencies

    US20080161182A1

  • Functional nanoscale metal oxides for stable metal single atom and cluster catalysts

    US20210016256A1

  • Catalyst

    US5480854A